Expandable thermoplastic composition, thermoplastic foam and method for producing same
By using cyclic ester thermoplastic foam materials and combining specific gas components, the challenges of polyester foam materials in the prior art in terms of density, strength and environmental protection are solved, and low-density, high mechanical strength and environmentally friendly foam materials are achieved.
Patent Information
- Application Number
- JP2024550335
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-23
- Filing Date
- 2023-02-23
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-02-23
AI Technical Summary
The prior art is difficult to develop environmentally friendly, economical and superior performance polyester thermoplastic foam materials, especially in achieving low density, high mechanical strength and closed cell structure.
A cyclic esters-based thermoplastic foam material is used, specifically including polymers with ethylene cyclone and optional vinyl ester lipid as the main components, and a low-density thermoplastic foam with hydrochloroxyethylene or fluoroclase containing three or four carbon atoms as gas components.
Low density and high mechanical strength of low-density thermoplastic foam materials are achieved, and the environmental protection and sustainability of the materials have been improved.
Smart Images

Figure 2025509117000119 
Figure 2025509117000120 
Figure 2025509117000121
Abstract
Description
[Technical field]
[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims the benefit of priority to and incorporates by reference U.S. Provisional Patent Application No. 63 / 312,855, filed February 23, 2022.
[0002] This application incorporates by reference U.S. Provisional Patent Application No. 63 / 343,990, filed May 19, 2022.
[0003] This application is also a continuation-in-part of, and incorporates by reference, each of, International Application Nos. PCT / US22 / 40504, filed Aug. 16, 2022, PCT / US22 / 40505, filed Aug. 16, 2022, PCT / US22 / 40506, filed Aug. 16, 2022, and PCT / US22 / 40507, filed Aug. 16, 2022.
[0004] FIELD OF THEINVENTION The present invention relates to foamable thermoplastic compositions, thermoplastic foams, foaming processes, and systems and articles made therefrom. [Background technology]
[0005] Foams are used in a wide variety of applications, and in many applications it is a desirable but difficult goal for the foam material to be environmentally friendly while at the same time having excellent performance properties and being cost-effective to produce. Environmental considerations include not only the recyclability and sustainability of the polymer resins that form the foam's structure, but also the low environmental impact of the blowing agents used to form the foam, such as the blowing agent's Global Warming Potential (GWP) and Ozone Depletion Potential (ODP).
[0006] Certain thermoplastic resin-based foams, including polyester resins, have been considered for their potential advantages in terms of recyclability and / or sustainable availability. However, difficulties have been encountered with the development of such materials. For example, it has been a challenge to develop polyester resins that are truly recyclable, can be produced from sustainable sources, and are compatible with blowing agents that can be combined with thermoplastics to produce foams with good performance properties. In many applications, performance properties that are considered highly desirable include the production of high-quality closed-cell foams that are low density (and therefore light in use) and at the same time have relatively high mechanical integrity and strength.
[0007] With regard to the choice of thermoplastic resin, EP 3,231,836 acknowledges that there has been interest in thermoplastic resins, particularly polyester-based resins, but that this interest has faced development difficulties, including the difficulty of identifying suitable foaming grades of such resins. Furthermore, EP 3,231,836 mentions that certain polyethylene terephthalate (PET) resins (including recycled PET) can be melt extruded with suitable physical and / or chemical blowing agents to obtain closed-cell foams with the potential for low density and good mechanical properties, but does not disclose that any of such resins are readily capable of producing foams with good environmental and performance properties, or that they can be formed from sustainable sources. The '836 application identifies several candidate polyester resins for use in forming open-cell foams, including polyethylene terephthalate, polybutylene terephthalate, polycyclohexane terephthalate, polyethylene naphthalate, polyethylene furanoate, or mixtures of two or more of these. While the use of polyester materials to create foams that have essentially no closed cells, as required by EP '836, can be beneficial for some applications, a drawback of such structures is that open-cell foams generally exhibit relatively poor mechanical strength properties.
[0008] China Patent No. 108484959 discloses that the production of foam products based on 2,5-furandimethyl copolyester is problematic due to alleged problems with the dissolution of the blowing agent in the polyester, and suggests certain processes including the use of a combination of liquid and gas blowing agents, and the sequential use of these different types of blowing agents.
[0009] US Patent Application Publication Nos. 2020 / 0308363 and 2020 / 0308396 each disclose the preparation of amorphous polyester copolymers, which includes starting with recycled polyester, exemplified only with PET as the main component, and then undergoing a series of processing steps to obtain an amorphous copolymer, i.e., a copolymer that does not have crystallinity. A wide variety of different types of blowing agents are mentioned for use with such amorphous polymers.
[0010] With respect to blowing agents, the common use of halogenated olefin blowing agents, including hydrofluoroolefins (HFOs) and hydrochlorofluoroolefins (HCFOs), is also known, for example, as disclosed in U.S. Patent Application Publication No. 2009 / 0305876, which is assigned to the assignee of the present invention and incorporated herein by reference. While the '876 application discloses the use of HFO and HFCO blowing agents with various thermoplastic materials to form foams, including PET, there is no disclosure or suggestion of the use of any of such blowing agents with any other type of polyester resin.
[0011] Applicants have come to realize that by using the polyester resins disclosed herein in combination with blowing agents comprising one or more hydrohaloolefins disclosed herein, one or more unexpected advantages may be achieved in connection with the formation of thermoplastic foams, particularly extruded thermoplastic foams. Summary of the Invention
[0012] The present invention relates to (a) thermoplastic polymer cells comprising cell walls forming closed cells, the thermoplastic polymer consisting essentially of ethylene furanoate moieties and optional ethylene terephthalate moieties, the polymer comprising from about 1 mol % to about 100 mol % ethylene furanoate moieties and optionally at least about 1 mol % ethylene terephthalate moieties; (b) one or more HFOs having 3 or 4 carbon atoms and / or one or more HFCOs having 3 or 4 carbon atoms contained within closed cells. For convenience, the foam according to this paragraph will be referred to herein as Foam 1A.
[0013] The present invention relates to (a) thermoplastic polymer cells comprising cell walls forming closed cells, the thermoplastic polymer having a crystallinity of at least about 5% and consisting essentially of ethylene furanoate moieties and optional ethylene terephthalate moieties, the polymer comprising from about 1 mol % to about 100 mol % ethylene furanoate moieties and optionally at least about 1 mol % ethylene terephthalate moieties; (b) one or more HFOs having 3 or 4 carbon atoms and / or one or more HFCOs having 3 or 4 carbon atoms contained within closed cells. For convenience, the foam according to this paragraph will be referred to herein as Foam 1B.
[0014] The present invention relates to (a) a thermoplastic polymer cell comprising cell walls forming closed cells, the thermoplastic polymer having a molecular weight of at least about 10,000 kg / mole and a crystallinity of at least about 5%, and consisting essentially of ethylene furanoate and ethylene terephthalate moieties, the polymer comprising from about 1 mol % to about 20 mol % ethylene furanoate moieties and at least about 1 mol % ethylene terephthalate moieties; (b) one or more HFOs having 3 or 4 carbon atoms and / or one or more HFCOs having 3 or 4 carbon atoms contained within closed cells. For convenience, the foam according to this paragraph will be referred to herein as Foam 1C.
[0015] The present invention relates to (a) thermoplastic polymer bubbles comprising cell walls forming closed cells, the thermoplastic polymer having a molecular weight of at least about 10,000 kg / mole and a crystallinity of at least about 5%, and consisting essentially of ethylene furanoate and ethylene terephthalate moieties, the polymer comprising from about 1 mol % to about 20 mol % ethylene furanoate moieties and from about 80 mol % to about 99 mol % ethylene terephthalate moieties; (b) one or more HFOs having 3 or 4 carbon atoms and / or one or more HFCOs having 3 or 4 carbon atoms contained within closed cells. For convenience, the foam according to this paragraph will be referred to herein as Foam 1D.
[0016] The present invention relates to (a) a thermoplastic polymer cell comprising cell walls forming closed cells, the thermoplastic polymer having a molecular weight of at least about 10,000 kg / mole and a crystallinity of at least about 5%, and consisting essentially of ethylene furanoate and ethylene terephthalate moieties, the polymer comprising from about 1 mol % to about 5 mol % ethylene furanoate moieties and from about 90 mol % to about 99 mol % ethylene terephthalate moieties; (b) one or more HFOs having 3 or 4 carbon atoms and / or one or more HFCOs having 3 or 4 carbon atoms contained within closed cells. For convenience, the foam according to this paragraph will be referred to herein as Foam 1E.
[0017] The present invention relates to (a) thermoplastic polymer bubbles comprising cell walls forming closed cells, the thermoplastic polymer having a molecular weight of at least about 10,000 kg / mole and a crystallinity of at least about 5%, and consisting essentially of ethylene furanoate and ethylene terephthalate moieties, the polymer comprising from about 1 mol % to about 5 mol % ethylene furanoate moieties and from about 95 mol % to about 99 mol % ethylene terephthalate moieties; (b) one or more HFOs having 3 or 4 carbon atoms and / or one or more HFCOs having 3 or 4 carbon atoms contained within closed cells. For convenience, the foam according to this paragraph will be referred to herein as Foam 1F.
[0018] The present invention relates to (a) thermoplastic polymer bubbles comprising cell walls forming closed cells, the thermoplastic polymer having a molecular weight of at least about 10,000 kg / mole and a crystallinity of at least about 5%, and consisting essentially of ethylene furanoate and ethylene terephthalate moieties, the polymer comprising from about 0.5 mol % to about 2 mol % ethylene furanoate moieties and from about 98 mol % to about 99.5 mol % ethylene terephthalate moieties; (b) one or more HFOs having 3 or 4 carbon atoms and / or one or more HFCOs having 3 or 4 carbon atoms contained within closed cells. For convenience, the foam according to this paragraph will be referred to herein as Foam 1G.
[0019] The present invention relates to (a) a thermoplastic polymer cell comprising cell walls forming closed cells, said thermoplastic polymer having a molecular weight of at least about 10,000 kg / mole and a crystallinity of at least about 5%, and consisting essentially of ethylene furanoate and ethylene terephthalate moieties, said polymer comprising about 1 mole % ethylene furanoate moieties and about 99 mole % ethylene terephthalate moieties; (b) one or more HFOs having 3 or 4 carbon atoms and / or one or more HFCOs having 3 or 4 carbon atoms contained within closed cells. For convenience, the foam according to this paragraph will be referred to herein as Foam 1H.
[0020] The present invention relates to (a) a thermoplastic polymer cell comprising cell walls forming closed cells, said thermoplastic polymer having a molecular weight of at least about 10,000 kg / mole and a crystallinity of at least about 5%, and consisting essentially of ethylene furanoate and ethylene terephthalate moieties, said polymer comprising about 0.5 mol % ethylene furanoate moieties and about 99.5 mol % ethylene terephthalate moieties; (b) one or more HFOs having 3 or 4 carbon atoms and / or one or more HFCOs having 3 or 4 carbon atoms contained within closed cells. For convenience, the foam according to this paragraph will be referred to herein as Foam 1I.
[0021] The present invention relates to (a) a thermoplastic polymer cell comprising cell walls forming closed cells, the thermoplastic polymer having a molecular weight of at least about 10,000 kg / mole and a crystallinity of at least about 5%, and consisting essentially of ethylene furanoate and ethylene terephthalate moieties, the polymer comprising about 5 mole percent ethylene furanoate moieties and about 95 mole percent ethylene terephthalate moieties; (b) one or more HFOs having 3 or 4 carbon atoms and / or one or more HFCOs having 3 or 4 carbon atoms contained within closed cells. For convenience, the foam according to this paragraph will be referred to herein as Foam 1J.
[0022] The present invention relates to (a) a thermoplastic polymer cell comprising cell walls forming closed cells, the thermoplastic polymer having a molecular weight of at least about 10,000 kg / mole and a crystallinity of at least about 5%, and consisting essentially of ethylene furanoate and ethylene terephthalate moieties, the polymer comprising about 10 mol % ethylene furanoate moieties and about 90 mol % ethylene terephthalate moieties; (b) one or more HFOs having 3 or 4 carbon atoms and / or one or more HFCOs having 3 or 4 carbon atoms contained within closed cells. For convenience, the foam according to this paragraph will be referred to herein as Foam 1K.
[0023] The present invention relates to (a) a thermoplastic polymer cell comprising cell walls forming closed cells, the thermoplastic polymer having a molecular weight of at least about 10,000 kg / mole and a crystallinity of at least about 5%, and consisting essentially of ethylene furanoate and ethylene terephthalate moieties, the polymer comprising about 20 mol % ethylene furanoate moieties and about 80 mol % ethylene terephthalate moieties; (b) one or more HFOs having 3 or 4 carbon atoms and / or one or more HFCOs having 3 or 4 carbon atoms contained within closed cells. For convenience, the foam according to this paragraph will be referred to herein as Foam 1L.
[0024] The present invention relates to (a) thermoplastic polymer cells comprising cell walls comprising polyethylene furanoate, wherein at least 25% of the cells are closed cells; (b) 1234ze(E) contained within closed cells. For convenience, foam according to this paragraph will be referred to herein as Foam 2A.
[0025] The present invention relates to (a) thermoplastic polymer cells comprising polyethylene furanoate and having cell walls consisting essentially of ethylene furanoate and ethylene terephthalate moieties, the polymer comprising from about 1 mol % to about 20 mol % ethylene furanoate moieties and about 0.5 mol % or more ethylene terephthalate moieties, at least 25% of the cells being closed cells; (b) 1234ze(E) contained within closed cells. For convenience, foam according to this paragraph will be referred to herein as Foam 2B.
[0026] The present invention relates to (a) thermoplastic polymer cells comprising polyethylene furanoate and having cell walls consisting essentially of ethylene furanoate and ethylene terephthalate moieties, the polymer comprising from about 1 mol % to about 20 mol % ethylene furanoate moieties and about 0.5 mol % or more ethylene terephthalate moieties, at least 25% of the cells being closed cells; (b) 1336mzz(Z) contained within closed cells. For convenience, foam according to this paragraph will be referred to herein as Foam 2C.
[0027] The present invention relates to (a) thermoplastic polymer cells comprising polyethylene furanoate and having cell walls consisting essentially of ethylene furanoate and ethylene terephthalate moieties, the polymer comprising from about 1 mol % to about 20 mol % ethylene furanoate moieties and about 0.5 mol % or more ethylene terephthalate moieties, at least 25% of the cells being closed cells; (b) 1223zd(E) contained within closed cells. For convenience, foams according to this paragraph will be referred to herein as foam 2D.
[0028] The present invention relates to (a) thermoplastic polymer cells comprising polyethylene furanoate and having cell walls consisting essentially of ethylene furanoate and ethylene terephthalate moieties, the polymer comprising from about 1 mol % to about 20 mol % ethylene furanoate moieties and about 0.5 mol % or more ethylene terephthalate moieties, at least 25% of the cells being closed cells; (b) 1224 yd contained within closed cells. For convenience, foam according to this paragraph will be referred to herein as foam 2E.
[0029] The present invention relates to (a) thermoplastic polymer cells comprising polyethylene furanoate and having cell walls consisting essentially of ethylene furanoate and ethylene terephthalate moieties, the polymer comprising from about 1 mol % to about 20 mol % ethylene furanoate moieties and about 0.5 mol % or more ethylene terephthalate moieties, at least 50% of the cells being closed cells; (b) a gas within said closed cells, said gas comprising about 25% to 100% by weight of 1234ze(E). For convenience, foams according to this paragraph are referred to herein as Foam 2F.
[0030] At various points in this specification, reference is made to a numbered foam (e.g., Foam 1) or group of numbered foams defined herein, and such reference refers to each such numbered series, e.g., each series having a number within the group, including any subscript numbered systems. For example, a reference to Foam 1 is understood to include a separate reference to each of Foams 1A, 1B, 1C, 1D, etc., and a reference to Foams 1-2 is understood to include a separate reference to each of Foams 1A, 1B, 1C, 1D, etc., and each of Foams 2A, 2B, 2C, 2D, etc. Furthermore, this convention is used throughout this specification for other defined materials, including blowing agents.
[0031] The present invention relates to (a) thermoplastic polymer bubbles comprising cell walls forming closed cells, the thermoplastic polymer consisting essentially of ethylene furanoate moieties and optional ethylene terephthalate moieties, the thermoplastic polymer comprising (i) about 10 mol % to about 100 mol % ethylene furanoate moieties, and optionally at least about 1 mol % ethylene terephthalate moieties, and (ii) having a molecular weight of at least about 25,000; (b) Trans 1234ze contained within closed cells. For convenience, foam according to this paragraph will be referred to herein as Foam 3.
[0032] The present invention relates to (a) thermoplastic polymer bubbles comprising cell walls forming closed cells, the thermoplastic polymer consisting essentially of ethylene furanoate moieties and optional ethylene terephthalate moieties, the thermoplastic polymer comprising (i) about 10 mol % to about 100 mol % ethylene furanoate moieties, and optionally at least about 1 mol % ethylene terephthalate moieties, and (ii) having a molecular weight of at least about 25,000 to about 140,000; (b) Trans 1234ze contained within closed cells. For convenience, foam according to this paragraph will be referred to herein as Foam 4.
[0033] The present invention relates to (a) a thermoplastic material consisting essentially of an ethylene furanoate portion and an optional ethylene terephthalate portion, the thermoplastic material comprising from about 1 mol % to about 100 mol % of an ethylene furanoate portion, and optionally at least about 1 mol % of an ethylene terephthalate portion; (b) a blowing agent comprising one or more HFOs having 3 or 4 carbon atoms and / or one or more HFCOs having 3 or 4 carbon atoms. For convenience, the foamable composition according to this paragraph will be referred to herein as Foamable Composition 1.
[0034] The present invention provides a method for forming a thermoplastic composition having improved crystallinity, comprising the steps of: (a) forming a thermoplastic material comprising polymer chains containing ethylene furanoate and / or ethylene terephthalate moieties; (b) dissolving at least a portion of the thermoplastic material, the thermoplastic material comprising about 1 mol % to about 100 mol % ethylene furanoate moieties, and optionally at least about 1 mol % ethylene terephthalate moieties, in a solvent; (c) distilling the solvent from the thermoplastic material. For convenience, the method of forming a thermoplastic composition according to this paragraph will be referred to herein as Thermoplastic Forming Method 1.
[0035] The present invention also provides a method for forming a thermoplastic foam comprising foaming a foamable composition of the present invention comprising Foamable Composition 1. For convenience, the method according to this paragraph is referred to herein as Foaming Method 1.
[0036] The present invention also provides a method for forming an extruded thermoplastic foam comprising extruding a foamable composition of the present invention comprising Foamable Composition 1. For convenience, the method according to this paragraph is referred to herein as Foaming Method 2.
[0037] The present invention also provides a method for forming an extruded thermoplastic foam, comprising extruding a foamable composition of the present invention comprising Foamable Composition 1. For convenience, the method according to this paragraph will be referred to herein as Extrusion Method 1. [Brief description of the drawings]
[0038] [Figure 1] FIG. 1 is a schematic diagram of an extrusion system and process according to one embodiment of the present invention and examples herein. [Figure 2A] 1 is a graphical representation of the results of Example C1B. [Figure 2B] 1 is a graphical representation of the results of Example C1B. [Figure 2C] 1 is a graphical representation of the results of Example C1B. [Figure 3A] 1 is a graphical representation of the results of Example C2B. [Figure 3B] 1 is a graphical representation of the results of Example C2B. [Figure 4] 1 is a graphical representation of the results of Example 1B. [Figure 5A] 1 is a graphical representation of the results of Example 2B. [Figure 5B] 1 is a graphical representation of the results of Example 2B. [Figure 6A] 1 is a graphical representation of the results of Example 3B. [Figure 6B] 1 is a graphical representation of the results of Example 3B. [Figure 6C] 1 is a graphical representation of the results of Example 3B. [Figure 6D] 1 is a graphical representation of the results of Example 3B. [Figure 7] 1 is a graphical representation of the results of Example 4B. [Figure 8] 1 is a graphical representation of the results of Example 5B. [Figure 9] 1 is a graphical representation of the results of Example 6B. [Figure 10] 1 is a graphical representation of the results of Example 7B. [Figure 11] 1 is a graphical representation of the results of Example 8B. [Figure 12] 1 is a graphical representation of the results of Example 9B. [Figure 13] 1 is a graphical representation of the results of Example 10B. [Figure 14] 1 is a graphical representation of the results of Example 11B. [Figure 15] 1 is a graphical representation of the results of Example 12B. [Figure 16] 1 is a graphical representation of the results of Example 12C. [Figure 17] 1 is a graphical representation of the results of Example 13B1. [Figure 18] 1 is a graphical representation of the results of Example 13B2. [Figure 19] 1 is a graphical representation of the results of Example 13B3. [Figure 20] 1 is a graphical representation of the results of Example 18. [Figure 21] 1 is a schematic diagram of an exemplary wind turbine. [Figure 22] 1 is a semi-schematic view of an exemplary wind turbine blade; [Figure 23A] 1 is a cross-sectional view of an exemplary wind turbine blade. [Figure 23B] 1 is a cross-sectional view of an exemplary wind turbine blade. [Figure 23C] 1 is a cross-sectional view of an exemplary wind turbine blade. [Figure 24] FIG. 2 is a cross-sectional view of an exemplary coated foam of the present invention in the particular form of a sandwich construction. [Diagram 25] 1 is a graphical representation of the results of Example 20. [Figure 26] 1 is a graphical representation of the results of Example 21.
[0039] definition 1234ze means 1,1,1,3-tetrafluoropropene without limitation regarding the isomeric form.
[0040] Trans 1234ze and 1234ze(E) each mean trans 1,3,3,3-tetrafluoropropene.
[0041] Cis 1234ze and 1234ze(Z) each represent cis 1,3,3,3-tetrafluoropropene.
[0042] 1234yf means 2,3,3,3-tetrafluoropropene.
[0043] 1233zd means 1-chloro-3,3,3-trifluoropropene without limitation regarding the isomeric forms.
[0044] Trans 1233zd and 1233zd(E) each represent trans 1-chloro-3,3,3-trifluoropropene.
[0045] 1224yd means cis 1-chloro-2,3,3,3-tetrafluoropropane without limitation with respect to isomeric forms.
[0046] 1336mzz means 1,1,1,4,4,4-hexafluorobutene without limitation with regard to the isomeric forms.
[0047] Trans 1336mzz and 1336mzz(E) each mean trans 1,1,1,4,4,4-hexafluorobutene.
[0048] Cis 1336mzz and 1336mzz(Z) each represent cis 1,1,1,4,4,4-hexafluorobutene.
[0049] By closed cell foam it is meant that a substantial volume percentage of the cells in the foam are closed, for example, about 20 volume percent or more.
[0050] The ethylene furanoate moiety refers to the following structure:
[0051] [ka]
[0052] FDCA means 2,5-furandicarboxylic acid and has the following structure:
[0053] [ka]
[0054] MEG means monoethylene glycol and has the following structure:
[0055] [ka]
[0056] FDME means dimethyl 2,5-furandicarboxylate and has the following structure:
[0057] [ka]
[0058] By PEF homopolymer is meant a polymer having at least 99 mole percent ethylene furanoate moieties.
[0059] By PEF copolymer is meant a polymer having at least about 10 mole percent ethylene furanoate moieties and greater than 1% polymer moieties other than ethylene furanoate moieties.
[0060] By PEF:PET copolymer is meant a polymer having at least about 10 mole percent ethylene furanoate moieties and at least 1% ethylene terephthalate moieties.
[0061] PEF means poly(ethylene furanoate) and is intended to encompass and reflect the description of PEF homopolymers and PEF copolymers.
[0062] The ethylene terephthalate moiety refers to the following structure:
[0063] [ka]
[0064] SSP stands for solid state polymerization.
[0065] PMDA means pyromellitic dianhydride, which has the following structure:
[0066] [ka] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0067] Poly(ethylene furanoate) The present invention relates to foams and foam articles comprising cell walls that include PEF segments.
[0068] The PEF forming the cell walls of the foams and foam articles of the present invention can be a PEF homopolymer or a PEF copolymer, particularly a PEF:PET copolymer.
[0069] PEF homopolymer is a known material that is known to be formed by either: (a) the esterification and polycondensation of FDCA with MEG, or (b) the transesterification and polycondensation of FDME with MEG, for example as shown below.
[0070] [ka]
[0071] A detailed description of such known esterification and polycondensation synthesis methods is provided in GB Patent No. 621971 (Drewitt, JGN and Lincoln, J., entitled "Improvements in Polymers"), which is incorporated herein by reference. A detailed description of such known transesterification and polycondensation synthesis methods is provided in Gandini, A., Silvestre, AJD, Neto, CP, Sousa, AF, and Gomes, M. (2009), "The furan counterpart of poly(ethylene terephthalate): an alternative material based on renewable resources.", J. Polym. Sci. Polym. Chem. 47, 295-298. doi:10.1002 / pola.23130, which is incorporated herein by reference.
[0072] Foam The foams of the present invention, including each of Foams 1-4, are formed from either PEF homopolymers, PEF copolymers, or combinations / blends thereof.
[0073] The foams of the present invention, including each of Foams 1-4, may in preferred embodiments be formed from a PEF homopolymer, where the polymer has at least 99.5% by weight, or at least 99.9% by weight, ethylene furanoate moieties.
[0074] It is contemplated that the foams of the present invention, including each of Foams 1-4, in preferred embodiments may be formed from a PEF copolymer, wherein the polymer, including the PEF copolymer, has about 60% to about 99% by weight ethylene furanoate moieties, or about 70% to about 99% by weight ethylene furanoate moieties, or about 80% to about 99% by weight ethylene furanoate moieties, or about 90% to about 99% by weight ethylene furanoate moieties, or about 95% to about 99.5% by weight ethylene furanoate moieties.
[0075] It is contemplated that the foams of the present invention, including each of Foams 1-4, in preferred embodiments may be formed from a PEF copolymer, wherein the polymer, including the PEF copolymer, has from about 40% to about 1% by weight ethylene furanoate moieties, or from about 30% to about 1% by weight ethylene furanoate moieties, or from about 20% to about 1% by weight ethylene furanoate moieties, or from about 10% to about 1% by weight ethylene furanoate moieties, or from about 5% to about 1% by weight ethylene furanoate moieties, or from about 5% to about 0.5% by weight ethylene furanoate moieties.
[0076] It is contemplated that the foams of the present invention, including each of Foams 1-4, in preferred embodiments may be formed from a PEF copolymer, wherein the polymer, including the PEF copolymer, has from about 40 mol % to about 1 mol % ethylene furanoate moieties, or from about 30 mol % to about 1 mol % ethylene furanoate moieties, or from about 20 mol % to about 1 mol % ethylene furanoate moieties, or from about 10 mol % to about 1 mol % ethylene furanoate moieties, or from about 5 mol % to about 1 mol % ethylene furanoate moieties, or from about 5 mol % to about 0.5 mol % ethylene furanoate moieties.
[0077] The foams of the invention, including each of Foams 1-4, in a preferred embodiment, are those in which the polymer comprising the PEF copolymer is from about 40 mol % to about 1 mol % ethylene furanoate moieties and from about 60 mol % to about 99 mol % ethylene terephthalate moieties, or from about 30 mol % to about 1 mol % ethylene furanoate moieties and from about 70 mol % to about 99 mol % ethylene terephthalate moieties, or from about 20 mol % to about 1 mol % ethylene furanoate moieties and from about 80 mol % to about 99 mol % ethylene terephthalate moieties. phthalate moieties, or about 10 mol % to about 1 mol % ethylene furanoate moieties and about 90 mol % to about 99 mol % ethylene terephthalate moieties, or about 5 mol % to about 1 mol % ethylene furanoate moieties and about 95 mol % to about 99 mol % ethylene terephthalate moieties, or about 5 mol % to about 0.5 mol % ethylene furanoate moieties and about 95 mol % to about 99.5 mol % ethylene terephthalate moieties.
[0078] For those embodiments of the invention that include PEF copolymers, it is believed that one of ordinary skill in the art, given the teachings contained herein, will be able to select the type and amount of copolymer material to be used within each of the ranges described herein to achieve the desired enhancement / modification of the polymer without undue experimentation.
[0079] With respect to those embodiments of the invention involving the use of PEF homopolymers or PEF copolymers, it is contemplated that such materials may be formed having a wide variety of molecular weights and physical properties within the scope of the invention. In a preferred embodiment, the foams, including each of Foams 1-4, are formed from PEFs having the ranges of properties specified in Table 1 below, measured as described in the Examples herein.
[0080] [Table 1]
[0081] In general, it is contemplated that one skilled in the art will be able to formulate PEF polymers within the above range of properties without undue experimentation in light of the teachings contained herein. However, in a preferred embodiment, PEFs (including PEF homopolymers and PEF copolymers) with these properties are achieved using one or more of the above synthesis methods in combination with various known supplemental processing techniques, including treatment with chain extenders such as PMDA (as well as alternatives and supplements to PMDA such as ADR, PENTA and talc described in the examples and elsewhere in this specification) and / or SSP processing. In light of the disclosure contained herein, including the polymer synthesis described in the examples below, and including the use of methods to enhance polymer crystallization, it is believed that one skilled in the art will be able to produce PEF polymers within the range of properties described in the above table and elsewhere in this specification. Such processing conditions include the methods to increase crystallization described herein, including the thermoplastic forming method 1 of the present invention, such methods being as disclosed in the examples herein.
[0082] An example of a process for chain extension treatment of polyesters is provided in the publication "Recycled poly(ethylene terephthalate) chain extension by a reactive extrusion process", Firas Awaja, Fugen Daver, Edward Kosior, 16 August 2004, https: / / doi.org / 10.1002 / pen.20155, which is incorporated herein by reference. As explained in US Patent Application Publication No. 1009 / 0264545, which is incorporated herein by reference, chain extenders are generally compounds that are typically at least difunctional with respect to reactive groups that can react with end groups or functional groups in the polyester to extend the length of the polymer chain. In certain cases, as disclosed herein, such treatments can advantageously increase the average molecular weight of the polyester to improve its melt strength and / or other important properties. The degree of chain extension achieved is related, at least in part, to the structure and functionality of the compound used. A variety of compounds are useful as chain extenders. Non-limiting examples of chain extenders include trimellitic anhydride, pyromellitic dianhydride (PMDA), trimellitic acid, its haloformyl derivatives, or compounds containing multifunctional epoxy (e.g., glycidyl) or oxazoline functional groups. Nanocomposite materials such as finely dispersed nanoclays may optionally be used to control viscosity. Commercially available chain extenders include CESA-Extend from Clariant, Joncryl from BASF, or Lotader from Arkema. The amount of chain extender may vary depending on the type and molecular weight of the polyester component. The amount of chain extender used to treat the polymer can vary widely, and in preferred embodiments ranges from about 0.1 to about 5 weight percent, or preferably from about 0.1 to about 1.5 weight percent. Examples of chain extenders are also described in U.S. Pat. No. 4,219,527, which is incorporated herein by reference.
[0083] An example of a process for SSP treatment of poly(ethylene furanoate) is provided in the article "Solid-State Polymerization of Poly(ethylene furanoate) Biobased Polyester, I: Effect of Catalyst Type on Molecular Weight Increase," by Nejib Kasmi, Mustapha Majdoub, George Z. Papageorgiou, Dimitris S. Achilias, and Dimitrios N. Bikiaris, which is incorporated herein by reference.
[0084] Particularly advantageous PEF thermoplastic polymers for making the foamable compositions and foams of the present invention are identified in the Thermoplastic Polymer Table below (Table 2A), all numerical values in the table are understood to be preceded by the word "about."
[0085] [Table 2]
[0086] Particularly advantageous PEF thermoplastic polymers for making the foamable compositions and foams of the present invention also include those materials identified in the Thermoplastic Polymers Table below (Table 2B), all numerical values in the table are understood to be preceded by the word "about."
[0087] [Table 3]
[0088] Particularly advantageous PEF thermoplastic polymers for making the foamable compositions and foams of the present invention also include those materials identified in the Thermoplastic Polymers Table below (Table 2C), all numerical values in the table are understood to be preceded by the word "about."
[0089] [Table 4-1]
[0090] [Table 4-2]
[0091] For the definition of terms used herein, it should be noted that at various points in this specification, reference is made to the thermoplastic polymers identified in the first column of each row of the TPP table above, and reference to each of these numbers is a reference to the thermoplastic polymer defined in the corresponding column of that row. Reference to a group of TPPs defined in the table above by reference to a TPP number means each such numbered TPP separately and individually, including each TPP having the indicated number, including any such number with a subscript. Thus, for example, reference to TPP1 is a separate and independent reference to TPP1A, TPP1B, TPP1C, TPP1D, and TPP1E. Reference to TPP1-TPP2 is a separate and independent reference to TPP1A, TPP1B, TPP1C, TPP1D, TPP1E, TPP2A, TPP2B, TPP2C, TPP2D, and TPP1E. This convention of usage is used in the foamable composition table and foam table below as well.
[0092] Foaming Agent As described in detail herein, the present invention includes, but is not limited to, Applicant's discovery that a select group of blowing agents can provide foamable PEF foamable compositions and PEF foams having a difficult to achieve and surprising combination of physical properties, including low density and good mechanical strength properties.
[0093] The blowing agent used in accordance with the present invention preferably comprises one or more hydrohaloolefins having 3 or 4 carbon atoms. For convenience, the blowing agent according to this paragraph may be referred to herein as Blowing Agent 1.
[0094] The blowing agent used in accordance with the present invention preferably comprises one or more of 1234ze, 1234yf, 1336mzz, 1233zd, and 1224ydf (hereinafter, for convenience, referred to as blowing agent 2), or comprises one or more of trans-1234ze, 1336mzz, trans-1233zd, and cis-1224yd (hereinafter, for convenience, referred to as blowing agent 3), or comprises one or more of trans-1234ze, trans-1336mzz, trans-1233zd, and cis-1224yd (hereinafter, for convenience, referred to as blowing agent 4), or comprises one or more of trans-1234ze, trans-1336mzz, trans-1233zd, and cis-1224yd (hereinafter, for convenience, referred to as blowing agent 5). Blowing agent 10 may contain one or more of 1234yf, 1234yd, 1224yd, 1234yf, 1234yd, 1233zd, or 1233zd.
[0095] Thus, it is contemplated that the blowing agents of the present invention, including each of Blowing Agents 1-11, may include, in addition to each of the blowing agents identified above, a co-blowing agent, including one or more of any potential co-blowing agents as described below. In a preferred embodiment, the foamable compositions, foams, and foaming methods of the present invention include a blowing agent as described herein, where the indicated blowing agent (including the compound or compounds specifically identified in each of Blowing Agents 1-11) is present in an amount of at least about 50% by weight, based on the total weight of all blowing agents present, or preferably at least about 60% by weight, preferably at least about 70% by weight, or preferably at least about 80% by weight, or preferably at least about 90% by weight, or preferably at least about 95% by weight, or preferably at least about 99% by weight, based on the sum of all blowing agent components.
[0096] The blowing agent used in accordance with the present invention also preferably consists essentially of one or more of 1234ze, 1234yf, 1336mzz, 1233zd, and 1224ydf (hereinafter, for convenience, referred to as blowing agent 12), or consists essentially of one or more of trans-1234ze, 1336mzz, trans-1233zd, and cis-1224yd (hereinafter, for convenience, referred to as blowing agent 13), or consists essentially of one or more of trans-1234ze, trans-1336mzz, trans-1233zd, and cis-1224yd (hereinafter, for convenience, referred to as blowing agent 14), or consists essentially of trans-1234ze and trans-1336mzz. 1336mzz (hereinafter, for convenience, referred to as blowing agent 15), or essentially consisting of trans-1234ze (hereinafter, for convenience, referred to as blowing agent 16), or essentially consisting of trans-1336mzz (hereinafter, for convenience, referred to as blowing agent 17), or essentially consisting of cis-1336mzz (hereinafter, for convenience, referred to as blowing agent 18), or essentially consisting of 1234yf (hereinafter, for convenience, referred to as blowing agent 19), or essentially consisting of 1224yd (hereinafter, for convenience, referred to as blowing agent 20), or essentially consisting of trans-1233zd (hereinafter, for convenience, referred to as blowing agent 21).
[0097] It is contemplated and understood that the blowing agents of the present invention, including each of Foaming Agents 1-21, may include one or more co-blowing agents not included in the selections shown, provided that the amounts of such co-blowing agents used do not impede or negate the ability to achieve relatively low density foams as described herein, including each of Foams 1-4, and preferably further do not impede or negate the ability to achieve foams having mechanical strength properties as described herein. Thus, in light of the teachings contained herein, it is believed that one of ordinary skill in the art, by way of example, can select one or more potential co-blowing agents of one or more saturated hydrocarbons or hydrofluorocarbons (HFCs), particularly C4-C6 hydrocarbons or C1-C4 HFCs, known in the art for use in a particular application without undue experimentation. Examples of such HFC co-blowing agents include, but are not limited to, one or combination of difluoromethane (HFC-32), fluoroethane (HFC-161), difluoroethane (HFC-152), trifluoroethane (HFC-143), tetrafluoroethane (HFC-134), pentafluoroethane (HFC-125), pentafluoropropane (HFC-245), hexafluoropropane (HFC-236), heptafluoropropane (HFC-227ea), pentafluorobutane (HFC-365), hexafluorobutane (HFC-356) and all isomers of all such HFCs. With respect to hydrocarbons, the blowing agent composition of the present invention may also include, in certain preferred embodiments, for example, iso, normal and / or cyclopentane, as well as butane and / or isobutane.Other materials may be included, such as water, CO2, CFCs (e.g., trichlorofluoromethane (CFC-11) and dichlorodifluoromethane (CFC-12)), hydrochlorocarbons (HCCs, such as dichloroethylene (preferably trans-dichloroethylene), ethyl chloride, and chloropropane), HCFCs, C1-C5 alcohols (e.g., ethanol and / or propanol and / or butanol, etc.), C1-C4 aldehydes, C1-C4 ketones, C1-C4 ethers (including ethers (e.g., dimethyl ether and diethyl ether), diethers (e.g., dimethoxymethane and diethoxymethane)), and methyl formate, organic acids (e.g., but not limited to, formic acid), including any combination thereof, although such components are not necessarily preferred in many embodiments due to their adverse environmental impact.
[0098] The blowing agent used in accordance with the present invention also preferably comprises one or more of 1234ze, 1234yf, 1336mzz, 1233zd, and 1224ydf (hereinafter, for convenience, referred to as blowing agent 22), or comprises one or more of trans1234ze, 1336mzz, trans1233zd, and cis1224yd (hereinafter, for convenience, referred to as blowing agent 23), or comprises one or more of trans1234ze, trans1336mzz, trans1233zd, and cis1224yd (hereinafter, for convenience, referred to as blowing agent 24), or comprises one or more of trans1234ze, trans1336mzz, trans1233zd, and cis1224yd (hereinafter, for convenience, referred to as blowing agent 25). ze and trans-1336mzz (hereinafter, for convenience, referred to as blowing agent 25), or consisting of trans-1234ze (hereinafter, for convenience, referred to as blowing agent 26), or consisting of trans-1336mzz (hereinafter, for convenience, referred to as blowing agent 27), or consisting of cis-1336mzz (hereinafter, for convenience, referred to as blowing agent 28), or consisting of 1234yf (hereinafter, for convenience, referred to as blowing agent 29), or consisting of 1224yd (hereinafter, for convenience, referred to as blowing agent 30), or consisting of trans-1233zd (hereinafter, for convenience, referred to as blowing agent 31).
[0099] Foams and Foaming Processes In general, foams of the invention, including each of Foams 1-4, or foams made from PEF polymers of the invention, including thermoplastic polymers TPP1A-TPP22E, or any of the foams described in Examples 1-22, can be formed from foamable compositions of the invention. In general, foamable compositions of the invention can be formed by combining a PEF polymer of the invention, including each of thermoplastic polymers TPP1A-TPP22E, with a blowing agent of the invention, including each of Blowing Agents 1-31.
[0100] Foamable compositions that fall within the scope of the present invention and that provide certain advantages in connection with forming the foams of the present invention are set forth in the following Foamable Composition Tables (Tables 3A and 3B), all numerical values in the tables are understood to be preceded by the word "about", and the following terms used in the tables have the following meanings:
[0101] CBAG1 means a co-blowing agent selected from the group consisting of 1336mzz(Z), 1336mzzm(E), 1224yd(Z), 1233zd(E), 1234yf, and combinations of two or more thereof.
[0102] CBAG2 means a co-blowing agent selected from the group consisting of water, CO2, C1-C6 hydrocarbons (HC), HCFCs, C1-C5 HFCs, C2-C4 hydrohaloolefins, C1-C5 alcohols, C1-C4 aldehydes, C1-C4 ketones, C1-C4 ethers, C1-C4 esters, organic acids, and combinations of two or more thereof.
[0103] CCBAG3 is a set of 10 ... 143), 1,1,1,2-tetrafluoroethane (HFC-134a), pentafluoroethane (HFC-125), pentafluoropropane (HFC-245), hexafluoropropane (HFC-236), heptafluoropropane (HFC-227ea), pentafluorobutane (HFC-365), hexafluorobutane (HFC-356), and combinations of any two or more thereof.
[0104] NR means not required.
[0105] [Table 5-1]
[0106] [Table 5-2]
[0107] [Table 5-3]
[0108] [Table 5-4]
[0109] [Table 5-5]
[0110]
Table 5-6
[0111]
Table 5-7
[0112]
Table 5-8
[0113]
Table 5-9
[0114]
Table 5-10
[0115]
Table 6-1
[0116]
Table 6-2
[0117]
Table 6-3
[0118]
Table 6-4
[0119] How to form vesicles It is contemplated that any one or more of a variety of known techniques for forming thermoplastic foams may be used to form the foams of the present invention, in light of the disclosure contained herein, and the foams of the present invention include each of Foams 1-4 and Foamable Compositions 1-11, all such techniques and all foams formed thereby, or all foams within the broad scope of the present invention. For clarity, it should be noted that the foam definitions in the table below all begin with the letter F only, in contrast to the foams defined by the Summary paragraph above, which begins with a capitalized Foamable Composition.
[0120] Generally, the forming process includes first introducing a blowing agent of the present invention, including each of Blowing Agents 1-31, to a PEF polymer of the present invention, including each of TPP1-TPP22, to form a foamable PEF composition including the PEF and the blowing agent. One preferred method for forming a foamable PEF composition of the present invention includes plasticizing the PEF, preferably by heating the PEF to, and preferably above, its melting temperature, and then exposing the PEF melt to the blowing agent under conditions effective to incorporate (preferably by solubilizing) a desired amount of the blowing agent into the polymer melt.
[0121] In a preferred embodiment, the foaming method of the present invention includes providing a foamable composition of the present invention containing each of FC1 to FC11, and foaming the provided foamable composition. In a preferred embodiment, the foaming method of the present invention includes providing a foamable composition of the present invention containing each of FC1 to FC11, and extruding the provided foamable composition to form a foam of the present invention containing each of Foams 1 to 4 and each of Foams F1 to F8.
[0122] The foaming process of the present invention can include batch processes, semi-batch processes, continuous processes, and combinations of two or more of these. Batch processes generally involve preparing at least a portion of a foamable polymer composition comprising each of FC1-FC11 in a storable state, and then using that portion of the foamable polymer composition to prepare a foam at some future time. Semi-batch processes involve preparing at least a portion of a foamable polymer composition comprising each of FC1-FC11, and intermittently expanding that foamable polymer composition into a foam comprising each of Foams 1-4 and each of Foams F1-F11, all in a single process. For example, U.S. Patent No. 4,323,528, incorporated herein by reference, discloses a process for making thermoplastic foams via an accumulative extrusion process. Thus, the present invention comprises a process comprising: 1) mixing a PEF thermoplastic polymer comprising each of TPP1-TPP22 with a blowing agent of the present invention comprising each of Blowing Agents 1-31 under conditions to form a foamable PEF composition; 2) extruding the foamable PEF composition comprising each of FC1-FC11 into a holding zone maintained at a temperature and pressure that will not foam the foamable composition, the holding zone preferably comprising a die defining an orifice opening into a zone of lower pressure where the foamable polymer composition comprising each of FC1-FC11 will foam, and an openable gate closing the die orifice; 3) periodically opening the gate to discharge the foamable polymer composition from the holding zone through the die orifice into the zone of lower pressure while substantially simultaneously applying mechanical pressure by a moveable ram to the foamable polymer composition comprising each of FC1-FC11; and 4) expanding the discharged foamable polymer composition under the influence of the blowing agent to form a foam comprising each of Foams 1-4 and each of Foams F1-F8.
[0123] The present invention may also use a continuous process to form the foam. By way of example, such a continuous process may include forming a foamable PEF composition comprising each of FC1-FC11, and then expanding the foamable PEF composition without substantial interruption. For example, a foamable PEF composition comprising each of FC1-FC11 may be prepared in an extruder by heating a selected PEF polymer resin comprising each of TPP1-TPP22 to form a PEF melt, incorporating a foaming agent of the present invention comprising each of Blowing Agents 1-31 into the PEF melt, preferably by solubilizing the blowing agent in the PEF melt at an initial pressure, to form a foamable PEF composition comprising a substantially homogenous combination of PEF and a blowing agent comprising each of FC1-FC11, and then extruding the foamable PEF composition through a die into a zone of selected foaming pressure, and foaming the foamable PEF composition to expand under the influence of the blowing agent into a foam comprising each of Foams 1-4 and each of Foams F1-F8 described below. Optionally, a foamable PEF composition comprising a PEF polymer, including each of FC1-FC11, and an incorporated blowing agent, including each of Blowing Agents 1-31, may be cooled prior to extruding the composition through a die to enhance certain desired properties of the resulting foam, including each of Foams 1-6 and each of Foams F1-F8.
[0124] The method can be carried out using, by way of example, the general type of extrusion apparatus disclosed in FIG. 1. Specifically, the extrusion apparatus can include a raw material feed hopper 10 for holding the inventive PEF polymer 15, including each of TPP1-TPP22, and one or more optional components, which can be added with the PEF in the hopper or optionally elsewhere in the process, depending on the specific needs of the user. The feed material 15, excluding the blowing agent, can be charged to the hopper and delivered to the screw extruder 10. The extruder 20 can include thermocouples (not shown) located at three points along its length and a pressure sensor (not shown) at the extruder discharge end 20A. A mixer section 30 can be located at the extruder discharge end 20A for receiving the inventive blowing agent components, including each of blowing agents 1-31, via one or more metering pumps 40A and 40B, and mixing these blowing agents into the PEF melt in the mixer section. Sensors (not shown) can be included to monitor the temperature and pressure of the mixer section 30. The mixer section 30 can discharge the inventive blowing agent composition melt, including each of FC1-FC11, into a pair of melt coolers 50 oriented in series, with temperature sensors (not shown) located at each cooler to monitor the melt temperature. The melt is then extruded through a die 60, which also has temperature and pressure sensors (not shown) for monitoring the pressure and temperature at the die. The die pressure and temperature can be varied according to the needs of each particular extrusion application to produce the inventive foams 70, including each of Foams 1-4 and each of Foams F1-F8 described below. The foams can then be conveyed away from the extrusion apparatus by a conveyor belt 80.
[0125] The foamable polymer compositions of the present invention, including each of FC1-FC11, may optionally contain additional additives such as nucleating agents, cell control agents, glass and carbon fibers, dyes, pigments, fillers, antioxidants, extrusion aids, stabilizers, antistatic agents, flame retardants, IR attenuating agents, and thermal insulation additives. Nucleating agents include materials such as talc, calcium carbonate, sodium benzoate, among others, and chemical blowing agents such as azodicarbonamide or sodium bicarbonate and citric acid. IR attenuating agents and thermal insulation additives may include carbon black, graphite, silicon dioxide, metal flakes or powders, among others. Flame retardants may include brominated materials such as hexabromocyclodecane and polybrominated biphenyl ethers, among others. Each of the additional optional additives described above may be introduced into the foam at various times and various places during the process according to known techniques, and all such additives and methods of addition are within the broad scope of the present invention.
[0126] Foam In a preferred embodiment, the foams of the present invention are formed in commercially available extrusion equipment and have the properties shown in Table 4 below, the values being measured as described in the Examples herein.
[0127] [Table 7]
[0128] Foams that fall within the scope of the present invention and provide certain advantages are set forth in Table 5 below, where all numerical values in the table are understood to be preceded by the word "about" and the symbol NR means "not required."
[0129] [Table 8-1]
[0130] [Table 8-2]
[0131]
Table 8-3
[0132]
Table 8-4
[0133]
Table 8-5
[0134]
Table 8-6
[0135]
Table 8-7
[0136]
Table 8-8
[0137]
Table 8-9
[0138]
Table 8-10
[0139]
Table 8-11
[0140]
Table 8-12
[0141]
Table 8-13
[0142]
Table 8-14
[0143]
Table 8-15
[0144]
Table 8-16
[0145]
Table 8-17
[0146]
Table 8-18
[0147]
Table 8-19
[0148]
Table 8-20
[0149]
Table 8-21
[0150]
Table 8-22
[0151]
Table 8-23
[0152] [Table 8-24]
[0153] [Table 8-25]
[0154] [Table 8-26]
[0155] [Table 8-27]
[0156] [Table 8-28]
[0157] The foams of the present invention have broad utility. The foams, including each of Foams 1-4 and Foams F1-F11, have unexpected advantages in applications requiring low density and / or good compressive and / or tensile and / or shear properties, and / or long term stability, and / or sustainably sourced, and / or made from recycled materials and recyclable. In particular, the foams, including each of Foams 1-6 and each of Foams F1-F8, have unexpected advantages in wind energy applications (wind turbine blades (shear web, shell, core, and root), marine applications (hulls, decks, superstructures, bulkheads, stringers, and interiors), industrial lightweight applications, automotive and transportation applications (interiors and exteriors of cars, trucks, trains, aircraft, and spacecraft).
[0158] The PEF:PET copolymer can be formed by any means known to those of skill in the art, including, but not limited to, the procedures described in the Examples herein.
[0159] The foams of the present invention, including each of Foams 1-4, are formed from either a PEF homopolymer, a PEF copolymer, a PEF:PET copolymer, or combinations / blends thereof.
[0160] The foams, including each of Foams 1-4, may in preferred embodiments be formed from a PEF homopolymer, where the polymer has at least 99.5% by weight, or at least 99.9% by weight, ethylene furanoate moieties.
[0161] It is contemplated that the foams of the invention, including each of Foams 1-3, may in a preferred embodiment be formed from a PEF copolymer, which is a polymer comprising a PEF copolymer having from about 10% by weight to about 99% by weight of an ethylene furanoate moiety. The invention includes foams, including each of Foams 1-3, wherein the thermoplastic polymer consists essentially of the components set forth in the table below.
[0162] [Table 9-1]
[0163] [Table 9-2]
[0164] Foams of the invention, including each of Foams 1-3, can include closed cell walls comprising each of the thermoplastic polymers of the invention, including each of TMP1-TMP12 listed in the table above.
[0165] For those embodiments of the invention involving PEF copolymers, it is believed that one of ordinary skill in the art, given the teachings contained herein, will be able to select the amount of type of copolymer material to be used within each of the ranges described herein to achieve the desired enhancement / modification of the polymer without undue experimentation.
[0166] It is contemplated that the TMPs of the present invention may be formed with a variety of physical properties, including the following ranges of polymer properties, measured as described in the Examples herein:
[0167] [Table 10]
[0168] In general, it is contemplated that one of ordinary skill in the art will be able to formulate PEF polymers within the above range of properties without undue experimentation in light of the teachings contained herein. However, in preferred embodiments, PEF polymers according to the present invention (including the PEF:PET copolymers of the present invention) having these properties are achieved using one or more of the above synthesis methods in combination with a variety of known auxiliary processing techniques, including treatment with chain extenders such as PMDA and / or SSP treatment.
[0169] An example of a process for chain extension treatment of polyesters is provided in the publication "Recycled poly(ethylene terephthalate) chain extension by a reactive extrusion process", Firas Awaja, Fugen Daver, Edward Kosior, 16 August 2004, https: / / doi.org / 10.1002 / pen.20155, which is incorporated herein by reference. As explained in US Patent Application Publication No. 1009 / 0264545, which is incorporated herein by reference, chain extenders are generally compounds that are typically at least difunctional with respect to reactive groups that can react with end groups or functional groups in the polyester to extend the length of the polymer chain. In certain cases, as disclosed herein, such treatments can advantageously increase the average molecular weight of the polyester to improve its melt strength and / or other important properties. The degree of chain extension achieved is related, at least in part, to the structure and functionality of the compound used. A variety of compounds are useful as chain extenders. Non-limiting examples of chain extenders include trimellitic anhydride, pyromellitic dianhydride (PMDA), trimellitic acid, its haloformyl derivatives, or compounds containing multifunctional epoxy (e.g., glycidyl) or oxazoline functional groups. Nanocomposite materials such as finely dispersed nanoclays may optionally be used to control viscosity. Commercially available chain extenders include CESA-Extend from Clariant, Joncryl from BASF, or Lotader from Arkema. The amount of chain extender may vary depending on the type and molecular weight of the polyester component. The amount of chain extender used to treat the polymer can vary widely, and in preferred embodiments ranges from about 0.1 to about 5 weight percent, or preferably from about 0.1 to about 1.5 weight percent. Examples of chain extenders are also described in U.S. Pat. No. 4,219,527, which is incorporated herein by reference.
[0170] An example of a process for SSP treatment of poly(ethylene furanoate) is given in the paper "Solid-State Polymerization of Poly(ethylene furanoate) Biobased Polyester, I: Effect of Catalyst Type on Molecular Weight Increase," Nejib Kasmi, Mustapha Majdoub, George Z. Papageorgiou, Dimitris S. Achilias, and Dimitrios N. Bikiaris, which is incorporated herein by reference.
[0171] Foaming Agent As described in detail herein, the present invention involves Applicant's discovery that a select group of blowing agents can provide foamable PEF compositions, including each of Foamable Compositions 1, and PEF foams, including each of Foams 1-3, that have difficult-to-achieve and surprising combinations of physical properties, including low density and good mechanical strength properties.
[0172] Thus, the blowing agent used in accordance with the present invention preferably comprises trans-1234ze (hereinafter, for convenience, referred to as blowing agent 1), or consists essentially of trans-1234ze (hereinafter, for convenience, referred to as blowing agent 2), or consists of trans-1234ze (hereinafter, for convenience, referred to as blowing agent 3). Thus, it is considered that the blowing agent of the present invention, particularly comprising blowing agents 1-2, may comprise a co-blowing agent in addition to trans-1234ze. Examples of possible co-blowing agents include 1234yf, 1336mzz, 1233zd and 1224yd. In preferred embodiments, the foamable compositions (including Foamable Composition 1), foams (including Foams 1-3), and foaming methods (including Foaming Method 1) of the present invention comprise a foaming agent, including Foaming Agents 1-3, and Trans 1234ze is present in an amount of at least about 50 wt.%, or preferably at least about 60 wt.%, preferably at least about 70 wt.%, or preferably at least about 80 wt.%, or preferably at least about 90 wt.%, or preferably at least about 95 wt.%, or preferably at least about 99 wt.%, based on the total weight of all blowing agents present.
[0173] One or more co-blowing agents not mentioned above may be included, provided that the amounts of such co-blowing agents used do not impede or negate the ability to achieve a relatively low density foam as described herein, and preferably do not further impede or negate the ability to achieve a foam having mechanical strength properties as described herein. Thus, in light of the teachings contained herein, it is believed that one of ordinary skill in the art will be able to select one or more possible co-blowing agents, by way of example, one or more saturated hydrocarbons or hydrofluorocarbons (HFCs), particularly C4-C6 hydrocarbons or C1-C4 HFCs, for use in a particular application without undue experimentation, as known in the art. Examples of such HFC co-blowing agents include, but are not limited to, one or combination of difluoromethane (HFC-32), fluoroethane (HFC-161), difluoroethane (HFC-152), trifluoroethane (HFC-143), tetrafluoroethane (HFC-134), pentafluoroethane (HFC-125), pentafluoropropane (HFC-245), hexafluoropropane (HFC-236), heptafluoropropane (HFC-227ea), pentafluorobutane (HFC-365), hexafluorobutane (HFC-356), and all isomers of all such HFCs. With respect to hydrocarbons, the blowing agent compositions of the present invention may also include, in certain preferred embodiments, for example, iso, normal and / or cyclopentane in thermoset foams, and butane or isobutane in thermoplastic foams.Other materials may be included, such as water, CO2, CFCs (e.g., trichlorofluoromethane (CFC-11) and dichlorodifluoromethane (CFC-12)), hydrochlorocarbons (HCCs, such as dichloroethylene (preferably trans-dichloroethylene), ethyl chloride, and chloropropane), HCFCs, C1-C5 alcohols (e.g., ethanol and / or propanol and / or butanol, etc.), C1-C4 aldehydes, C1-C4 ketones, C1-C4 ethers (including ethers (e.g., dimethyl ether and diethyl ether), diethers (e.g., dimethoxymethane and diethoxymethane)), and methyl formate, organic acids (e.g., but not limited to, formic acid), including any combination thereof, although such components are not necessarily preferred in many embodiments due to their adverse environmental impact.
[0174] Foams and Foaming Processes The foams of the present invention are thermoplastic foams, and generally, any one or more of a variety of known techniques for forming thermoplastic foams may be used in light of the disclosure contained herein, and it is contemplated that all such techniques and all foams formed thereby or within the broad scope of the present invention may be used.
[0175] Generally, the forming step involves introducing a blowing agent to a PEF according to the invention to form a foamable PEF composition comprising the PEF and the blowing agent. One preferred method for forming such a foamable composition involves plasticizing the PEF, preferably by heating the PEF to, and preferably above, its melting temperature, and then exposing the PEF melt to the blowing agent under conditions effective to incorporate (preferably by solubilizing) a desired amount of the blowing agent into the polymer melt.
[0176] The foaming process of the present invention includes batch processes, semi-batch processes, continuous processes, and combinations of two or more thereof. A batch process generally involves preparing at least a portion of a foamable polymer composition in a storable state, and then using that portion of the foamable polymer composition to prepare a foam at some future time. A semi-batch process involves preparing at least a portion of a foamable polymer composition, and intermittently foaming the foamable polymer composition into a foam, all in a single process. For example, U.S. Patent No. 4,323,528, incorporated herein by reference, discloses a process for making thermoplastic foams via an accumulative extrusion process. The present invention thus comprises a process comprising: 1) mixing a PEF thermoplastic polymer with a blowing agent of the present invention under conditions to form a foamable PEF composition; 2) extruding the foamable PEF composition into a holding zone maintained at a temperature and pressure that will not foam the foamable composition, the holding zone preferably including a die defining an orifice opening into a zone of lower pressure where the foamable polymer composition foams, and an openable gate closing the die orifice; 3) periodically opening the gate to discharge the foamable polymer composition from the holding zone through the die orifice into the zone of lower pressure while substantially simultaneously applying mechanical pressure to the foamable polymer composition by a moveable ram; and 4) expanding the discharged foamable polymer composition under the influence of a blowing agent to form a foam.
[0177] The present invention can also use a continuous process to form the foam. By way of example, such a continuous process includes forming a foamable PEF composition and then expanding the foamable PEF composition without substantial interruption. For example, the foamable PEF composition can be prepared in an extruder by heating a selected PEF polymer resin to form a PEF melt, incorporating a blowing agent of the present invention into the PEF melt, preferably by solubilizing the blowing agent in the PEF melt at an initial pressure, to form a foamable PEF composition comprising a substantially homogenous combination of PEF and blowing agent, and then extruding the foamable PEF composition through a die into a zone of a selected foaming pressure, and foaming the foamable PEF composition to expand under the influence of the blowing agent into a foam. Optionally, the foamable PEF composition comprising the PEF polymer and the incorporated blowing agent may be cooled before extruding the composition through a die to enhance certain desired properties of the resulting foam.
[0178] The foamable composition according to the preferred embodiment of the present invention may optionally contain additional additives such as nucleating agents, cell control agents, dyes, pigments, fillers, antioxidants, extrusion aids, stabilizers, antistatic agents, flame retardants, IR attenuating agents and thermal insulation additives. Nucleating agents include materials such as talc, calcium carbonate, sodium benzoate, among others, and chemical blowing agents such as azodicarbonamide or sodium bicarbonate and citric acid. IR attenuating agents and thermal insulation additives may include carbon black, graphite, silicon dioxide, metal flakes or powders, among others. Flame retardants may include brominated materials such as hexabromocyclodecane and polybrominated biphenyl ethers, among others. Each of the above-mentioned additional optional additives may be introduced into the foam at various times and various places during the process according to known techniques, and all such additives and methods of addition are within the broad scope of the present invention.
[0179] In a preferred embodiment, the foams of the present invention are formed on commercially available extrusion equipment and have the properties shown in the table below, where the values are measured as shown in the table and supplemented in the "Examples" section of this specification, and are understood to be modified by "about."
[0180] [Table 11]
[0181] The foams of the present invention have broad utility. The foams of the present invention, including each of Foams 1-3, have unexpected advantages in applications requiring low density and / or good compressive and / or tensile and / or shear properties, and / or long-term stability, and / or sustainable sourcing, and / or being made from recycled materials and recyclable. In particular, the foams of the present invention, including each of Foams 1-3, have unexpected advantages in wind energy applications (wind turbine blades (shear webs, shells, cores, and nacelles), marine applications (hulls, decks, superstructures, bulkheads, stringers, and interiors), industrial lightweight applications, automotive and transportation applications (interiors and exteriors of cars, trucks, trains, aircraft, and spacecraft). EXAMPLES
[0182] Without limiting the full scope of the invention, applicants conducted a series of experiments for the purpose of demonstrating the utility of the PEF homopolymers and PEF-based copolymers of the invention and comparing the performance of the inventive foams made according to the invention to foams made from PET. These tests included the synthesis of a series of PET polymers covering a range of physical properties such as molecular weight, crystallinity and melting point. Applicants also prepared a series of PEF polymers (including homopolymers and copolymers) across a similar range of physical properties. A series of foams was produced using the highly preferred 1234ze(E) as the blowing agent. Foams prepared using other halogenated C3 and C4 olefin blowing agents according to the invention were also tested. A consistent set of processing conditions was utilized for a given range of comparable polymer properties. The details of each of these experimental series results are described in detail in the Examples below. In summary, the following table provides some of the important polymer properties, processing conditions, and an indication of the advantages of the inventive foams over comparable foams made with PET homopolymer.
[0183] [Table 12-1]
[0184] [Table 12-2]
[0185] [Table 12-3]
[0186] As shown by the table above, for each polymer, a unique temperature pair (for melting and pre-foaming) was identified for the foaming experiments. These temperatures and all other conditions, except for the amount of blowing agent, were kept substantially constant to generate strength data as a function of polymer expansion or foam relative density (RFD) in these foaming experiments. The foaming conditions were selected to ensure adequate expansion.
[0187] The foams thus produced were tested throughout the examples of this application to determine the density of the foams using a method generally corresponding to ASTM D71, except that hexane was used as a substitute for water. To facilitate comparison of the densities of the foams produced in these examples, applicants report the foam density as a relative foam density (RFD), which is the density of the foam measured as above divided by the density of the starting polymer. All foam densities herein, whether they are derived from PEF or PET homopolymers, or from PEF-PET copolymers, are corrected by the density of PEF polymer, 1.43 g / cc, which is about 7% less dense than PET. In this way, when the strengths of various polymer foams are compared at the same RFD, they are also compared at the same overall density.
[0188] Additionally, each of the foams produced in these examples was tested to determine tensile and compressive strength, which were measured according to the guidelines set forth in ASTM C297 and ISO 844, respectively, with each measurement being performed in the direction of reduced pressure.
[0189] After making these measurements, Applicants have determined that the foam produced in Example C3B4-1 below exhibited compressive strengths comparable to those expected for a commercially available PET foam sample tested under Applicants' experimental conditions (110 kg / m 3 ) to the foam of Example C2B4-1. Thus, to facilitate comparison of the test results provided herein, the tensile and compressive strength values of the foam produced in Example C2B4-1 were set to a baseline value of 1, respectively, and all other foam strength results reported in these examples are reported on a relative basis to the foam of C2B4-1 as relative tensile strength ("RTS") and relative compressive strength ("RCS"). For example, a foam measured to have a tensile strength two times greater than the tensile strength measured for Example C2B4-1 would be reported as having an RTS of 2.
[0190] Comparative Example C1A - Preparation of PET homopolymer with a molecular weight of 105.3 kg / mol using PMDA and SSP 1 Homopolymers of PET with molecular sizes from about 105 kg / mol were made using the additives and polymer formation procedures described in Synthesis Example C1A below. 1 The designation of an example herein as "Comparative" should not be construed as indicating that the example represents any item of prior art, but instead is merely presented for purposes of comparison with preferred aspects of the invention that are presented in other examples.
[0191] The homopolymer thus produced, designated PETC1, was tested and found to have the characteristics reported in Table C1 below. 2
[0192] [Table 13] 2 Throughout these examples, the molecular weights determined and referenced herein refer to molecular weight determination by diffusion-ordered nuclear magnetic resonance spectroscopy (DOSY NMR) according to the description contained in "Application of 1H DOSY NMR in Measurement of Polystyrene Molecular Weights" VNU Journal of Science: Natural Sciences and Technology, Vol. 36, No. 2 (2020) 16-21 June 2020, Nam et al., except that the solvent used was different. The above reference used 3 mg of polystyrene and 0.5 mL of deuterated chloroform. In these examples, NMR measurements were performed using a dissolved portion of 2-3 mg of polymer in a mixture of 0.6 mL of 50% by volume deuterated chloroform + 50% by volume trifluoroacetic acid.
[0193] Comparative Example C1B - Preparation of PET foam using PET1A with 1234ze(E) blowing agent at 60 minutes melt time In one series of experiments, one gram of polymer (shown in Table C1A above) in a glass container was placed in a 60cc capacity autoclave and then dried under vacuum at elevated temperatures ranging from 130°C to 150°C for 6 hours. The dried polymer was then cooled to room temperature. In each case, the blowing agent (shown in Table C1B below) was then pumped into the autoclave containing the dried polymer, followed by heating the autoclave to bring the polymer to a molten state, the pressure of which is listed in Table C1B below as the melt pressure. The PET / blowing agent mixture was maintained in the molten state at the melt state pressure and temperature for about 60 minutes (hereafter referred to as the "melt time"), and then the melt / blowing agent temperature and pressure were reduced to the pre-expansion temperature and pre-expansion pressure shown in Table C1B over a period of about 5-15 minutes. The autoclave was then maintained at approximately this temperature and pressure for about 30 minutes to ensure that the amount of blowing agent incorporated in the melt under such conditions reached equilibrium. The conditions used, such as the amount of blowing agent and the melt temperature and pressure, were determined after several trials based on the ability to form acceptable foams with RFD values ranging from about 0.05 to about 0.15.The temperature and pressure in the autoclave were then rapidly reduced (about 10 seconds for pressure reduction, about 1-10 minutes for temperature reduction using cold water) to ambient conditions (about 22°C and 1 atm) and foaming was allowed to occur.
[0194] Thus, the foam produced in this Comparative Example 1B was tested and found to have the properties as reported in Table C1B below.
[0195] [Table 14]
[0196] The relative tensile strength, relative compressive strength, and combined relative tensile strength and compressive strength results (hereafter referred to as "RTS+RCS") for the foams reported in Table C1B above are plotted as a function of relative foam density (RFD) in Figures 2A-2C, with the dashed lines used to show the linear representation of the tensile strength data as a function of relative foam density.
[0197] The graph above shows the generally expected increase in tensile and compressive strength of PET foam as the foam density increases over this density range (the dashed line constitutes the linear trend of the data).
[0198] Comparative Example 2A - Preparation of PET homopolymers with molecular weights ranging from 80 to 96 kg / mol and crystallinity of 32 to 43 using PMDA and SSP Using the procedures described in Synthesis Example C2A1, Synthesis Example C2A2, Synthesis Example C2A3, and variations thereof to achieve a polymer having a molecular weight of 83,900, designated below as PETC2A4, four PET homopolymers were prepared by polycondensation resulting in polymer products having molecular sizes ranging from about 80 kg / mole to about 96 kg / mole.
[0199] The PET polymers, designated herein as PETC2A1, PETC2A2, PETC2A3 and PETC2A4, were tested and found to have the properties as reported in Table C2A below.
[0200] [Table 15]
[0201] As can be seen from the table above, each of the PET homopolymers was produced utilizing the preferred high crystallinity embodiment of the present invention, thus including unexpectedly high strength in the PET foam produced using the blowing agent of the present invention compared to a PET foam produced from a PET polymer that does not utilize this embodiment of the present invention, as shown by comparing with the results of Comparative Example 1A.
[0202] Comparative Example 2B: Preparation of PET foams using PETC2A1, PETC2A2, PETC2A3 and PETC2A4 with 1234ze(E) blowing agent at 60 minute melt time In a series of experiments, 1 gram of each polymer (shown in Table C2A above) in a glass container was placed in a 60cc capacity autoclave and then dried under vacuum at elevated temperatures ranging from 130°C to 150°C for 6 hours. The dried polymer was then cooled to room temperature. In each case, the blowing agent (shown in Table C2B below) was then pumped into the autoclave containing the dried polymer, followed by heating the autoclave to bring the polymer to a molten state, the temperature, pressure and time being listed in Table C2B below. In this regard, it should be noted that the melt time for the experiment was 60 minutes. After the melt time shown, the melt / blowing agent temperature and pressure were then reduced to the pre-expansion temperature and pre-expansion pressure shown in Table C2B over a period of about 5-15 minutes. The autoclave was then maintained at approximately this temperature and pressure for about 30 minutes to ensure that the amount of blowing agent incorporated in the melt under such conditions reached equilibrium. The conditions used, such as the amount of blowing agent and the melt temperature and pressure, were determined after several trials based on the ability to form acceptable foams with RFD values ranging from about 0.05 to about 0.2. The temperature and pressure in the autoclave were then rapidly reduced (about 10 seconds for pressure reduction, about 1-10 minutes for temperature reduction using cold water) to ambient conditions (about 22° C. and 1 atm) and foaming was allowed to occur.
[0203] Thus, the PET foam produced in this Example C2B was tested and found to have the properties as reported in Table C2B below.
[0204] [Table 16]
[0205] The unexpected ability to achieve relatively low density, high strength PET foams with relatively high molecular weight and improved crystallinity using preferred blowing agents of the present invention, including the HFO-1234ze blowing agent used in this example, is shown in Figures 3A and 3B, which compare the TS and RTS+RCS results of the C2B1, C2B2 and C2B3 data of this comparative example with Comparative Example 1B.
[0206] The data provided by this example demonstrates aspects of Applicant's invention related to the unexpected advantages achieved by forming high strength, low density thermoplastic foams, including both PET and PEF foams (including PEF copolymers), with relatively high crystallinity. In particular, by utilizing a PET polymer with about 20% higher, and even more preferably about 30% higher, crystallinity, as in Example C2B, the tensile strength and RTS+RCS of the foam are unexpectedly improved by about 2-fold, even compared to a polymer with a high molecular weight but low crystallinity (i.e., 13.9%).
[0207] Example 1A - Preparation of PEF homopolymers with MW of about 41-75 kg / mol and crystallinity of 36%-42% using PMDA and SSP Using the additives and polymer formation procedures described in Synthesis Examples 1A1 and 1A2, two homopolymers of PEF were made, yielding polymer products with molecular sizes ranging from about 41 kg / mol to about 75 kg / mol.
[0208] The PEF polymers, designated herein as PEF1A1 and PEF1A2, were tested using the measurement protocol described in Comparative Example 1A above and found to have the properties reported in Table E1A below.
[0209] [Table 17]
[0210] The PEF polymers produced in these examples are referred to in Table E1 above and hereinafter as PEF1A1 and PEF1A2.
[0211] Example 1B - Preparation of PEF foams using PEF1A1 and PEF1A2 with Trans 1234ze blowing agent at 60 min melt time Using a foaming process designed using the same criteria as described in Comparative Example 1B, one foam was made using PEF1A1 and four foams were made using PEF1A2, as described herein. The foams so produced were tested and found to have the properties reported in Table E1B below.
[0212] [Table 18]
[0213] As evidenced by the data in Table E1B above, Applicants have surprisingly found that PEF foams according to the present invention have unexpectedly higher tensile and compressive strength values as measured by RTS+RCS compared to PET foams at approximately comparable crystallinity (based on trend lines), even though the PET foams use high crystallinity values according to the present invention and have substantially higher molecular weights than the PEF foams. This is shown, for example, in Figure 4 by comparison with the trend lines for foams made from PET of Comparative Example 1A over a range of relative foam densities from 0.04 to 0.13, especially considering that the molecular weight of the PEF foam of this example is substantially lower than that of the PET foam.
[0214] As evidenced by the graph above and all of the examples presented herein, the PEF foam of the present invention exhibits dramatically superior strength properties compared to PET foam. With particular reference to the graph above, the PEF foam of the present invention is substantially stronger than PET foam (having the same range of crystallinity) even though the molecular weight of the PEF foam is substantially lower than that of the PET foam, even though the strength of the foam generally increases with increasing molecular weight. Thus, for example, the trend line of PEF in the graph above at an RFD of about 0.08 has a RTS+RCS 1.3 times greater than the PET trend line based on PET foam made at a much higher molecular weight. This result is highly advantageous and unexpected.
[0215] Example 2A - Preparation of PEF homopolymer with MW in the range of about 90-96 kg / mol (using PMDA and SSP) Using the additives and polymer formation procedures described in Synthesis Examples 2A1 and 2A2, two homopolymers of PEF were made, yielding polymer products with molecular sizes ranging from about 90 kg / mol to about 96 kg / mol.
[0216] The PEF polymer so produced was tested using the measurement protocol described in Comparative Example 1A above and found to have the properties reported in Table E2A below.
[0217] [Table 19]
[0218] The PEF polymers produced in these examples are referred to in Table E2A above and hereinafter as PEF2A1 and PEF2A2.
[0219] Example 2B - Preparation of PEF foams using PEF1A1 and PEF1A2 with Trans 1234ze blowing agent at 60 min melt time Using a foaming process designed using the same criteria as described in Comparative Example 1B, three foams were made using PEF2A1 and one foam was made using PEF2A2, as described herein. The foams so produced were tested and found to have the properties as reported in Table E2B below.
[0220] [Table 20]
[0221] As evidenced by the data in Table E1B above, Applicants have surprisingly found that PEF foams according to the present invention have unexpectedly high tensile strength and RTS+RCS values. This is illustrated, for example, by reference to the foam formed from the PET of Comparative Example 2A, as shown in Figures 5A and 5B. The graph below includes the PET data of Table C2B and trend lines for all of the PET data of Table C2B for comparison purposes.
[0222] As can be seen from the results of this example, the PEF homopolymer foams of the present invention unexpectedly provide superior strength compared to PET homopolymer foams made using the same foam-forming techniques of the present invention with the preferred HFO-1234ze blowing agent of the present invention.
[0223] One unexpected advantage of the present invention illustrated by this example is the significantly higher relative tensile strength and RTS+RCS of the foams, as summarized in Table E2C below.
[0224] [Table 21]
[0225] The results summarized in Table E1C above are particularly unexpected considering that the PET foams of this example have not been disclosed in the prior art, i.e., the PET results incorporate a preferred embodiment of the invention using a preferred blowing agent of the invention, i.e., HFO-1234ze(E), for the formation of foams from relatively high crystallinity and high molecular weight polymers. In addition, PEF-based foams blown with HFO-1234ze(E) of the invention also unexpectedly outperform PEF-based foams of the invention when blown with other halogenated olefin blowing agents, as shown in Example 14 herein.
[0226] Example 3A - Preparation of PET9:PEF1 Copolymer with MW of approximately 117.9 kg / mol using PMDA A block copolymer of PET9:PEF1 (9:1 molar ratio) with a target molecular weight of about 117,900 g / mol for the PET portion of the copolymer was prepared using the additives and polymer formation procedure as described in Synthesis Example 3A.
[0227] The PET9:PEF1 copolymer so produced was tested using the measurement protocol described in Comparative Example 1A above, and found to have the properties reported in Table E3A below.
[0228] [Table 22]
[0229] The PET9:PEF1 copolymer so produced is referred to in these examples as PET9PEF1-EX3A.
[0230] Example 3B - Preparation of PEF foam using PET9PEF1-EX3A with Trans 1234ze blowing agent at 60 min melt time Six foams were made from PET9PEF1-EX3A using a foaming process designed using the same criteria as described in Comparative Example 1. The foams so produced were tested and found to have the properties as reported in Table E3B below.
[0231] [Table 23]
[0232] As evidenced by the data in Table E3B above, Applicants have surprisingly discovered that foams made with PET9:PEF1-EX3B in accordance with the present invention have unexpectedly high strength properties.
[0233] 6A-6D show the average tensile strength values of the foams in three density regions, namely, RFD ranges of (i) 0.056-0.062, (ii) 0.077-0.079, and 0.171-0.177, as shown in Table E3B above, and include the average data in the same regions of the PET data in Table C2B for comparison purposes.
[0234] As can be seen from the results of this example, the PET9:PEF1 copolymer foams of the present invention provide unexpectedly superior strength over a wide range of relative densities, as exemplified by this example in terms of the significantly higher relative tensile strength and significantly higher compressive strength of the foams. The extent of this unexpected advantage, particularly for this example, is summarized in Table E3C below.
[0235] [Table 24]
[0236] The context of these results includes the fact that the comparative examples incorporate preferred aspects of the present invention relating to the formation of foams from relatively high crystallinity and high molecular weight polymers and the preferred blowing agent of the present invention (i.e., HFO-1234ze(E)).
[0237] Comparative Example 3B: Preparation of PET foam using PETC2A1 and PETC2A2 with 1234ze(E) blowing agent at 15 minute melt time In a series of experiments, 1 gram of each polymer (shown in Table C2A for PETC2A1 and PETC2A2 above) in a glass container was placed in a 60cc capacity autoclave and then dried under vacuum for 6 hours at elevated temperatures ranging from 130°C to 150°C. The dried polymer was then cooled to room temperature. In each case, the blowing agent (shown in Table C3B below) was then pumped into the autoclave containing the dried polymer, followed by heating the autoclave to bring the polymer to a molten state, the temperature, pressure and time being listed in Table C3B below. In this regard, it should be noted that the melt time for the experiment was 15 minutes. After the melt time shown, the melt / blowing agent temperature and pressure were then reduced to the pre-expansion temperature and pre-expansion pressure shown in Table C3B over a period of about 5 to 15 minutes. The autoclave was then maintained at approximately this temperature and pressure for about 30 minutes to ensure that the amount of blowing agent incorporated in the melt under such conditions reached equilibrium. The conditions used, such as the amount of blowing agent and the melt temperature and pressure, were determined after several trials based on the ability to form acceptable foams with RFD values ranging from about 0.05 to about 0.2. The temperature and pressure in the autoclave were then rapidly reduced (about 10 seconds for pressure reduction, about 1-10 minutes for temperature reduction using cold water) to ambient conditions (about 22° C. and 1 atm) and foaming was allowed to occur.
[0238] Thus, the PET foam produced in this Example C3B was tested and found to have the properties as reported in Table C3B below.
[0239] [Table 25]
[0240] Example 4B - Preparation of PEF foam using PEF2A2 with Trans 1234ze blowing agent at 15 min melt time Using PEF2A2 as described in Table E2A and using a foaming process designed using the same criteria as described in Comparative Example 1B, six foams were made using the same basic process except that the melt time was 15 minutes. The foams so produced were tested and found to have the properties as reported in Table E4B below.
[0241] [Table 26]
[0242] As evidenced by the data in Table E4B above, applicants have surprisingly found that PEF foams according to the present invention have unexpectedly high tensile and compressive strength values. This is illustrated, for example, by reference to the foam formed from PET in Comparative Example C3B2, and illustrated by the following graph, particularly in view of the fact that the Comparative Example incorporates a preferred embodiment of the present invention relating to the formation of a foam from a relatively high crystallinity and high molecular weight polymer and the preferred blowing agent of the present invention (i.e., HFO-1234ze(E)). Figure 7 shows the results of the foam data in the RFD region of about 0.116.
[0243] As can be seen from the results of this example, the PEF homopolymer foams of the present invention provide unexpectedly superior strength compared to PET homopolymer foams made using the same foam-forming techniques of the present invention with the preferred HFO-1234ze blowing agent of the present invention. For example, with respect to the significantly higher relative tensile strength and RTS+RCS of the foams, as illustrated by this example. In particular, the extent of this unexpected advantage is summarized in Table E4C below.
[0244] [Table 27]
[0245] Example 5A - Preparation of PET9:PEF1 Copolymer with MW of about 45 kg / mol and CR% of 28.6 using PMDA A block copolymer of PET9:PEF1 (9:1 molar ratio) with a target molecular weight of about 45,000 g / mole for the PET portion of the copolymer was prepared using the additive, polymer formation procedure as described in Synthesis Example 5Ae below.
[0246] The PET9:PEF1 copolymer so produced was tested using the measurement protocol described in Example 1A above, and found to have the properties reported in Table E5A below.
[0247] [Table 28]
[0248] The PET9:PEF1 copolymer so produced is referred to in these examples as PET9PEF1-EX5A.
[0249] Example 5B - Preparation of PEF foam using PET9PEF1-EX5A with Trans 1234ze blowing agent at 15 min melt time Two types of foams were made from PET9PEF1-EX5A using a foaming process designed using the same criteria as described in Comparative Example 1. The foams so produced were tested and found to have the properties as reported in Table E5B below.
[0250] [Table 29]
[0251] As evidenced by the data in Table E5B above, Applicants have surprisingly discovered that foams made with PET9:PEF1-EX5B in accordance with the present invention have unexpectedly high strength properties.
[0252] FIG. 8 shows the strength values of the foams compared to the average values (reported in Table C3B above) for PETC3B2 foam in the same density regions encompassed in Table E5B above, namely about 0.05-0.06 and about 0.13-0.15.
[0253] As can be seen from the results of this example, the PET9:PEF1 copolymer foams of the present invention provide unexpectedly superior strength as shown by this example with respect to significantly higher RCS in the region of RFD from about 0.06 to about 0.14. The extent of this unexpected advantage, particularly for this example, is summarized below in Table E5C.
[0254] [Table 30]
[0255] Examples 6A1 and 6A2 - Preparation of PET99:PEF1 copolymers with PET MW of about 92-97 kg / mol and Cr% of 28.8-33.5 using PMDA and SSP Two random copolymers of PET99:PEF1 (99:1 molar ratio) with target molecular weights of about 92 and 97 kg / mol for the PET portion and a target molecular weight of about 45,000 g / mol for the PET portion of the copolymer were prepared using the additive and polymer formation procedures described in Synthesis Example 6A1 below, or modifications thereof, to achieve a polymer with a target molecular weight of 92,160.
[0256] The PET99:PEF1 copolymer was tested and found to have the properties in Table E6A.
[0257] [Table 31]
[0258] The PET99:PEF1 copolymers so produced are referred to in these examples as PET99PEF1-EX6A1 and PET99PEF1-EX6A2.
[0259] Example 6B - Foam preparation using PET99PEF1-EX6A1 and A2 with Trans 1234ze blowing agent at 15 minute melt time Six foams were made from PET99PEF1-EX6B using a foaming process designed using the same criteria as described in Comparative Example 1. The foams so produced were tested and found to have the properties as reported in Table EB below.
[0260] [Table 32]
[0261] As evidenced by the data in Table E6B above, Applicants have surprisingly found that foams made with PET99:PEF1-EX6A1 and EX6A2 in accordance with the present invention have unexpectedly high strength properties.
[0262] FIG. 9 shows the tensile strength values, compressive strength values, and combined tensile plus compressive strength values for the foams shown in Table E6B above, and includes data for the PET data in Table C1B for comparative purposes.
[0263] As can be seen from the results of this example, the PET99:PEF1 copolymer foams of the present invention provide unexpectedly superior strength, as shown, for example, by comparison with the PET homopolymer foam made in Comparative Example 1 using the preferred HFO-1234ze blowing agent of the present invention. As can be seen from the results of this example, the PET99:PEF1 homopolymer foams of the present invention provide unexpectedly superior strength, as compared to PET homopolymer foams made using the same foam-forming techniques of the present invention including the preferred HFO-1234ze blowing agent of the present invention. Notably, the extent of this unexpected advantage is summarized below in Table E6C.
[0264] [Table 33]
[0265] Example 7A1 - Preparation of PET19:PEF1 copolymer with PET MW of about 46 kg / mol and Cr% of 30.2 using PMDA A random copolymer of PET19:PEF1 (19:1 molar ratio) with a target molecular weight of the PET portion of about 46 kg / mol was prepared using the same additives and basic polymer formation procedure as described in Synthesis Example 8A below, modified to produce a target PET molecular weight of about 46 kg / mol.
[0266] The PET19:PEF1 copolymer was tested and found to have the properties in Table E7A.
[0267] [Table 34]
[0268] The PET19:PEF1 copolymer so produced is referred to in this example as PET19PEF1-EX7A1.
[0269] Example 7B - Foam preparation using PET19PEF1-EX7A1 with Trans 1234ze blowing agent at 15 minute melt time Foams were made from PET19PEF1-EX7A using a foaming process designed using the same criteria as described in Comparative Example 1. The foams so produced were tested and found to have the properties as reported in Table E7B below.
[0270] [Table 35]
[0271] As evidenced by the data in Table E7B above, applicants have found that foams made with PET19:PEF1-EX7A1 according to the present invention have superior strength properties. For example, foams made with the relatively low density copolymers of the present invention have strength values that compare favorably to the average results of PET homopolymer foams identified as C3B2-14 (having an RFD of 0.063) and C3B2-2 (having an RFD of 0.088) in Table C3B above, which have nearly double the molecular weight of the PET19:PEF1 copolymer of the present invention. This unexpected result is shown in Figure 10 for RTS+RCS.
[0272] Given that the molecular weight of PET homopolymer is more than twice that of the inventive PET19:PEF1, the comparable strength values of PET19:PEF1 are unexpected.
[0273] Examples 8A1 and 8A2 - Preparation of PET19:PEF1 copolymers with PET MW of about 72-79 kg / mol and 27.62-32% using PMDA and SSP Two random copolymers of PET19:PEF1 (19:1 molar ratio) with target molecular weights of the PET portion of about 72 kg / mol and about 79 kg / mol were prepared using the additives and polymer formation procedures described in Synthesis Examples 8A1 and 8A2.
[0274] The PET19:PEF1 copolymer was tested and found to have the properties in Table E8A.
[0275] [Table 36]
[0276] The PET19:PEF1 copolymers so produced are referred to in this example as PET19PEF1-EX8A1 and PET19PEF1-EX8A2.
[0277] Example 8B - Foam preparation using PET19PEF1-EX8A1 and EX8A2 with Trans 1234ze blowing agent at 15 minute melt time Foams were made from each of PET19PEF1-EX8A1 and EX8A2 using a foaming process designed using the same criteria as described in Comparative Example 1. The foams so produced were tested and found to have the properties as reported in Table E8B below.
[0278] [Table 37]
[0279] As evidenced by the data in Table E8B above, applicants have found that foams made with PET19:PEF1-EX8A1 and EX8A2 according to the present invention have superior strength properties. For example, the foams of the present invention, having an average RFD of 0.091, exhibit strength values that compare favorably to the PET homopolymer foams identified as C3B1-2 and C3B2-2 in Table C3B above, and have the same average density as compared to the RFD of the PET19:PEF1 copolymer of this example. This unexpected result is shown in FIG. 11.
[0280] Given that the crystallinity of PET homopolymer is 1.3 times higher than that of PET19:PEF1 and the MW of PET homopolymer is 1.2 times higher than the MW of PET19:PEF1 in this example, it is entirely unexpected that the strength values of PET19:PEF1 are comparable to foams formed from PET homopolymer, and it is especially unexpected that the relative compressive strength of the present invention is greater than that of PET homopolymer, resulting in combined RTS+CTS values that are also greater than that of PET homopolymer.
[0281] Example 9A1 - Preparation of PET19:PEF1 copolymer with PET MW of about 62 kg / mol and Cr% of 26.1 using PMDA and SSP A random copolymer of PET19:PEF1 (19:1 molar ratio) with a target molecular weight of the PET portion of about 62 kg / mole was prepared using the same additives and basic polymer formation procedure as described in Synthesis Example 8A below, modified to produce a target PET molecular weight of about 62 kg / mole.
[0282] The PET19:PEF1 copolymer was tested and found to have the properties in Table E9A.
[0283] [Table 38]
[0284] The PET19:PEF1 copolymer so produced is referred to in this example as PET19PEF1-EX9A1.
[0285] Example 9B - Foam preparation using PET19PEF1-EX9A1 with Trans 1234ze blowing agent at 15 minute melt time Foams were made from PET19PEF1-EX9A using a foaming process designed using the same criteria as described in Comparative Example 1. The foams so produced were tested and found to have the properties as reported in Table E9B below.
[0286] [Table 39]
[0287] As evidenced by the data in Table E9B above, applicants have found that foams made with PET19:PEF1-EX9A1 according to the present invention have superior strength properties. For example, foams made with the relatively low density copolymers of the present invention have strength values that compare favorably to the PET homopolymer foam identified as C3B1-3 in Table C3B above, which has a density of 0.104 and thus is very close to the density of the PET19:PEF1 copolymer of the present invention. This unexpected result is shown in FIG.
[0288] Given that the molecular weight of PET homopolymer is more than 1.5 times greater than the molecular weight of PET19:PEF1 of the present invention, it is entirely unexpected that each of the reported strength values for PET19:PEF1 are essentially equivalent to the strength values of PET homopolymer.
[0289] Example 10A - Preparation of PET19:PEF1 Copolymer with PET MW of about 79 kg / mol and Cr% of 32.4 using PMDA and SSP A random copolymer of PET19:PEF1 (19:1 molar ratio) with a target molecular weight of the PET portion of about 79 kg / mol was prepared using the additives and basic polymer formation procedure described in Synthesis Example 8A below, modified to produce a target PET molecular weight of about 79 kg / mol.
[0290] The PET19:PEF1 copolymer was tested and found to have the properties in Table E10A.
[0291] [Table 40]
[0292] The PET19:PEF1 copolymer so produced is referred to in this example as PET19PEF1-EX10A.
[0293] Example 10B - Foam preparation using PET19PEF1-EX10A with Trans 1234ze blowing agent at 15 minute melt time Foams were made from PET19PEF1-EX10A using a foaming process designed using the same criteria as described in Comparative Example 1. The foams so produced were tested and found to have the properties as reported in Table E10B below.
[0294] [Table 41]
[0295] As evidenced by the data in Table E10B above, applicants have found that foams made with PET19:PEF1-EX10A according to the present invention have excellent strength properties. For example, the foam of this example had a density of 0.13, but exhibited strength values that were well comparable to a PET homopolymer of substantially the same density but with a much higher molecular weight. In particular, the PET homopolymer foam identified as C3B1-4 in Table C3B above had a density of 0.129 and a 20% higher molecular weight than the PET19:PEF1 copolymer used to make the foams of the present invention. Nevertheless, as shown in FIG. 13, the strength values of the two foams are unexpectedly comparable.
[0296] It is entirely unexpected that each of the reported strength values for PET19:PEF1 are nearly identical to those of PET homopolymer, given that the molecular weight of PET homopolymer is approximately 20% greater than the molecular weight of the present invention PET19:PEF1.
[0297] Example 11A - Preparation of PET19:PEF1 Copolymer with PET MW of about 83 kg / mol and Cr% of 20.7 using PMDA and SSP A block copolymer of PET19:PEF1 (19:1 molar ratio) with a target molecular weight of the PET portion of about 83 kg / mol was prepared as described in Synthesis Example 11A below.
[0298] The PET19:PEF1 copolymer was tested and found to have the properties of Table E11A.
[0299] [Table 42]
[0300] The PET19:PEF1 copolymer so produced is referred to in this example as PET19PEF1-EX11A.
[0301] Example 11B - Foam preparation using PET19PEF1-EX10A with Trans 1234ze blowing agent at 15 minute melt time Foams were made from PET19PEF1-EX11A using a foaming process designed using the same criteria as described in Comparative Example 1. The foams so produced were tested and found to have the properties as reported in Table E11B below.
[0302] [Table 43]
[0303] As evidenced by the data in Table E11B above, applicants have found that foams made with PET19:PEF1-EX11A according to the present invention have excellent strength properties. For example, the foam in this example was made from a copolymer having a PET portion with a molecular weight of about 83 kg / mol and a crystallinity of about 21%, yet exhibited strength values that fully matched or exceeded the strength of a PET homopolymer made from a polymer of substantially the same density but with a 1.2 times higher molecular weight and 1.6 times higher crystallinity. In particular, the PET homopolymer foam identified as C3B1-4 in Table C3B above had a density of 0.129 and had a relative compressive strength substantially lower than the compressive strength of the lower density PET19:PEF1 data in this example, as shown, for example, in FIG. 14.
[0304] Given that the molecular weight of PET homopolymer is about 20% higher than that of the PET19:PEF1 of the present invention, and has about 60% higher crystallinity, it is quite unexpected that each of the reported strength values for PET19:PEF1 are nearly the same as or slightly higher than those of PET homopolymer.
[0305] Examples 12A1 and 12A2 - Preparation of PET9:PEF1 copolymers with MW of about 57-69 kg / mol and CR% of 28-34 using ADR and PMDA, talc, SSP Two block copolymers of PET9:PEF1 (9:1 molar ratio) with target molecular weights of the PET portion of the copolymers from about 57 to about 69 kg / mol were prepared using additives and polymer formation procedures as described in Synthesis Examples 12A1 and 12A2.
[0306] The PET9:PEF1 copolymer so produced was tested using the measurement protocol described in Comparative Example 1A above, and found to have the properties reported in Table E12A below.
[0307] [Table 44]
[0308] The PET9:PEF1 copolymers so produced are referred to in these examples as PET9PEF1-EX12A1, PET9PEF1-EX12A2 and PET9PEF1-EX12A3.
[0309] Example 12B - Preparation of PEF foam using PET9PEF1-EX12A1 with Trans 1234ze blowing agent at 15 min melt time Three types of foams were made from PET9PEF1-EX12A1 using a foaming process designed using the same criteria as described in Example 5A. The foams so produced were tested and found to have the properties as reported in Table E12B1 below.
[0310] [Table 45]
[0311] As evidenced by the data in Table E12B above, Applicants have surprisingly found that foams made with PET9:PEF1-EX12A1 in accordance with the present invention have unexpectedly high strength properties.
[0312] FIG. 15 shows foam strength values compared to PET9:PEF1 foam made with PMDA in Example 5 in the same density regions encompassed in Table E5B above, namely about 0.05-0.06 and about 0.13-0.15.
[0313] As can be seen from the results of this example, PET9:PEF1-EX12 produced an acceptable foam with good expansion.
[0314] Example 12C - Preparation of PEF foam using PET9PEF1-EX12A2 with Trans1234ze blowing agent at 15 min melt time Foams were made from PET9PEF1-EX12A2 using a foaming process designed using the same criteria as described in Example 5A. The foams so produced were tested and found to have the properties as reported in Table E12B2 below.
[0315] [Table 46]
[0316] As evidenced by the data in Table E12B2 above, Applicants have surprisingly found that foams made with PET9:PEF1-EX12A2 according to the present invention have unexpectedly high strength properties.
[0317] FIG. 16 shows foam strength values compared to PET9:PEF1 foam made with PMDA in Example 5 in the density region between the density regions shown in Table E5B above, i.e., from about 0.055 to about 0.144.
[0318] As can be seen from the results of this example, PET9:PEF1-EX12 produced an acceptable foam with good expansion.
[0319] Examples 13A1 and 13A2 - Preparation of PET9:PEF1 and PET19:PEF1 copolymers with MW of about 47-12 kg / mol using PMDA and SSP A first block copolymer of PET9:PEF1 (9:1 molar ratio) with a target molecular weight of about 47 kg / mol for the PET portion and PET and PEF oligomer blocks of 1-5(monomer), 1-5(monomer) was prepared using the PENTA additive as described in Synthesis Example 13A in conjunction with the polymer formation procedure to achieve a target molecular weight of 47,030, or using a modification of Synthesis Example 13A to achieve a target molecular weight of about 45,000 or about 12,000 kg / mol.
[0320] The PET:PEF copolymer so produced was tested using the measurement protocol described in Example 1A above, and found to have the properties reported in Table E13A below.
[0321] [Table 47]
[0322] The PET9:PEF1 copolymers so produced are referred to in these examples as PET9PEF1-EX13A1, PET9PEF1-EX13A2 and PET9PEF1-EX13A3, as shown in Table E13A above.
[0323] Example 13B1 - Preparation of PEF foam using PET9PEF1-EX13A1 with Trans 1234ze blowing agent at 15 minutes melt time Foams were made from PET9PEF1-EX13A1 using a foaming process designed using the same criteria as described in Comparative Example 5, except that PENTA was used instead of PMDA. The foams so produced were tested and found to have the properties as reported in Table E13B below.
[0324] [Table 48]
[0325] As evidenced by the data in Table E13B1 above, Applicants have surprisingly discovered that foams made with PET9:PEF1-EX13A1 according to the present invention have unexpectedly high strength properties.
[0326] FIG. 17 shows foam strength values compared to PET9:PEF1 foam made with PMDA in Example 5 in the foam density region shown in Table E5B above, which has a value of about 0.055.
[0327] As can be seen from the results of this example, PET9:PEF1-EX12 produced an acceptable foam with good expansion.
[0328] Example 13 Preparation of PET19:PEF1 Copolymer with MW of about 45 kg / mol using B2-PENTA Foams were made from PET19PEF1-EX13A2 using a foaming process designed using the same criteria as described in Example 7, except that PENTA was used instead of PMDA. The foams so produced were tested and found to have the properties as reported in Table E13B2 below.
[0329] [Table 49]
[0330] As evidenced by the data in Table E13B2 above, Applicants have surprisingly found that foams made with PET9:PEF1-EX13A2 according to the present invention have unexpectedly high strength properties.
[0331] FIG. 18 shows foam strength values compared to PET9:PEF1 foam made with PMDA in Example 7 in the foam density region shown in Table E7B above with a value of about 0.08.
[0332] As can be seen from the results of this example, PET9:PEF1-EX12 produced an acceptable foam with good expansion.
[0333] Example 13 Preparation of PET19:PEF1 Copolymer with MW of about 11.69 kg / mol using B3-PENTA and SSP Foams were made from PET19PEF1-EX13A3 using a foaming process designed using the same criteria as described in Example 9B, except that PENTA was used instead of PMDA. The foams so produced were tested and found to have the properties reported in Table E13B3 below.
[0334] [Table 50]
[0335] As evidenced by the data in Table E13B3 above, Applicants have surprisingly found that foams made with PET9:PEF1-EX13A3 according to the present invention have unexpectedly high strength properties.
[0336] FIG. 19 shows foam strength values compared to PET9:PEF1 foam made with PMDA in Example 9 in the foam density region shown in Table E97B above, which has a value of about 0.107.
[0337] As can be seen from the results of this example, PET9:PEF1-EX12 produced an acceptable foam with good expansion.
[0338] Example 14B - Preparation of PET9:PEF1 foam using PET9:PEF1_Ex3A and trans-123zd, trans-1233zd, and cis-1336 blowing agents and a 60 minute melt time A series of foams using PET9:PEF1_Ex3A were made using a foaming process designed using the same criteria as described in Comparative Example 1B. The foams so produced were tested and found to have the properties as reported in Table E14B below.
[0339] [Table 51]
[0340] As evidenced by the data in Table E1B above, Applicants have surprisingly found that PET:PEF foams according to the present invention, when the blowing agent comprises, consists essentially of, or consists of 1234ze(E), generally have superior strength properties as evidenced by the data in the table above, compared to other blowing agents such as 1233zd and 1336. Nevertheless, when the blowing agent comprises, consists essentially of, or consists of 1233zd(E) or 1336mzz(Z), acceptable foams are produced and have substantial utility, as evidenced by the above data.
[0341] Comparative Example 4A - Preparation of 46.4 kg / mol Molecular Weight PET Homopolymer Using PMDA and SSP PET homopolymer was prepared using the same design conditions specified in Comparative Example 1, except that the process conditions were targeted to produce a polymer molecular weight in the range of 40,000-50,000 g / mol. As in Comparative Example 1, the polymer was treated with 0.7 wt. % of the chain extender PMDA, according to known techniques, and then subjected to solid state polymerization as described in Comparative Example 1 to produce the PET homopolymer. The PET homopolymer was tested and found to have the characteristics as reported in Table C4A below.
[0342] [Table 52]
[0343] The PET polymer so produced is referred to as PETC4A in these examples.
[0344] Comparative Example 4B - Preparation of PET Foam Using PETC4A with 1234ze(E) Blowing Agent After drying at 130°C under vacuum for 6 hours, two types of foams were made by charging 1 gram of polymer (shown in Table C4B below) in a glass container into an autoclave and then cooling to room temperature. For each polymer, the blowing agent (shown in Table C4B below) was then pumped into the autoclave containing the dried polymer, followed by heating the autoclave to bring the polymer to the molten state and pressure shown in Table C4B. The PET / blowing agent mixture was maintained in the molten state for about 1 hour, and then the melt / blowing agent temperature and pressure were reduced to the pre-expansion temperature and pre-expansion pressure shown in Table C4B over a period of about 5-15 minutes. The autoclave was then maintained at about this temperature and pressure for about 30 minutes to allow the amount of blowing agent incorporated in the melt under such conditions to reach equilibrium. The conditions used, such as the amount of blowing agent and the melt temperature and pressure, were determined after several trials based on the ability to form acceptable foams having RFD values of about 0.2 or less. The temperature and pressure inside the autoclave were then rapidly reduced (approximately 10 seconds for pressure reduction and approximately 1-10 minutes for temperature reduction using cold water) to ambient conditions (approximately 22° C. and 1 atm) to induce foaming.
[0345] The foam produced in this Comparative Example 4 was tested and found to have the properties as reported in Table C4B below.
[0346] [Table 53]
[0347] Example 15A - Preparation of PEF homopolymer with MW of about 49 kg / mol using PMDA and SSP The same additives and basic polymer formation procedure used to form the PET homopolymer of Comparative Example 3 were used to make the PEF homopolymer, achieving a polymer molecular weight of about 49,000 g / mole. Specifically, the 49 kg / mole MW PEF homopolymer was formed by esterification and polycondensation of 75 grams of 2,5-furandicarboxylic acid (FDCA) with 59.8 grams of monoethylene glycol (EG). The reactants were added to a 500 mL cylindrical steel reactor equipped with an overhead stirrer and a distillation / condensation apparatus. After pulling a vacuum and backfilling with nitrogen, 0.067 grams of titanium (IV) isopropoxide catalyst was added to the flask. The flask was then lowered into a salt bath at 180° C. and overhead mixing was started at 200 rpm under a nitrogen atmosphere. After 2.5 hours, the bath temperature was increased to 220° C. After 30 minutes at this temperature under nitrogen, the vacuum was started. After 40 minutes under vacuum, the temperature was increased to 230° C. and continued for 1 hour. Under a nitrogen flow, 0.58 grams (0.7 wt%) of PMDA was slowly added over a period of about 5 minutes. To carry out the SSP, an aliquot (30 g) of the product was ground and heated in a rotary evaporator under vacuum at 180° C. for 3 days to produce the PEF homopolymer reported below. The PEF homopolymer was tested using the same measurement techniques as described in Comparative Example 1 and found to have the properties reported in Table E15 below.
[0348] [Table 54]
[0349] The PEF polymer so produced is referred to as PEF15A in Table E3 and in the examples that follow.
[0350] Example 15B - Preparation of PEF Foam Using PEF3 and Trans 1234ze as Blowing Agent Three foams were made from PEF2, as described herein, using a foaming process designed using the same criteria as described in Comparative Example 1. The foams so produced were tested and found to have the properties reported in Table 15A below.
[0351] [Table 55]
[0352] The first observation regarding the test results as shown in the table above is that for PET foams, decreasing the molecular weight to 46.5K resulted in a substantial decrease in foam strength compared to PET foams made from higher molecular weight PET. As an example, comparative example C2G, which used 83.9K molecular weight PET, produced a foam with an RFD of 0.09 and an RTS of 1.0. The 46.5 PET foam of this example, even with the higher RFD, produced a foam with an RTS less than half that value.
[0353] Surprisingly, foams made with low molecular weight PEFs did not show a substantial decrease in tensile strength compared to PEF foams made with high molecular weight PEFs. This result is unexpected. As a result, the tensile strength of foams made from PEF homopolymers with a molecular weight of 49K and 1234ze(E) blowing agent was dramatically better than foams made from PET homopolymers with a molecular weight of 46.5K and 1234ze(E) blowing agent. This unexpected result can be shown, for example, by observing that the average RFD of three PEF data points according to the present invention results in an average density of 0.079 and an average relative tensile strength of 1.34. Nevertheless, compared to PET foams with densities over 200% greater than the average PEF foam density, the PEF foams of the present invention produce an average tensile strength that is 4 times greater than the average relative tensile strength of high density PET foams (0.35). This is a very important and unexpected result.
[0354] Example 16 - Preparation of PET9:PEF1 Copolymer with MW of about 133.8 kg / mol using PMDA and SSP A random copolymer of PET9:PEF1 (9:1 molar ratio) was prepared by adding 8.7 grams (0.0472 moles) of furandicarboxylic acid methyl ester (FDME), 106.8 grams (0.42 moles) of bis(2-hydroxyethyl) terephthalate (BHET), and 6.2 grams (0.1 moles) of EG to a 500 mL cylindrical steel reactor equipped with an overhead stirrer and distillation / condensation apparatus. After evacuating and backfilling with N2, 0.046 grams of Ti(IV) isopropoxide catalyst was added. The reactor was then placed in a salt bath at 180°C and overhead mixing was started at 200 rpm under N2 atmosphere. After 2.5 hours, the bath temperature was increased to 220°C. After 30 minutes under N2, vacuum was started. After 40 minutes under vacuum, the temperature was increased to 250°C and continued for 40 minutes. Under N2 atmosphere, 0.59 grams of PMDA (0.0.0027 moles) was slowly added. After mixing for an additional 30 minutes at temperature, the reaction was stopped. An aliquot (30 g) of the above product was ground and then subjected to solid state polymerization by heating in a rotary evaporator at 180°C under vacuum for 3 days. The PEF polymer was tested and found to have the characteristics of Table E7.
[0355] [Table 56]
[0356] The PET9:PEF1 random copolymer so produced is referred to in these examples as PET9PEF1-EX16.
[0357] Examples 16B1-16B3: Preparation of PETPEF copolymer foams using PET9PEF1-EX16B and Trans1234ze as the blowing agent Three types of foams were made from PET9PEF1-EX16B using a foaming process designed using the same criteria as described in Comparative Example 1. The foams so produced were tested and found to have the properties as reported in Table E16B below.
[0358] [Table 57]
[0359] As evidenced by the data in Table E16B above, Applicants have surprisingly found that foams made from PEF9:PET1-EX16B in accordance with the present invention have unexpectedly superior tensile strength than foams formed from PET homopolymers, as shown by FIG. 20, which includes PET tensile strength data from comparative examples for comparison purposes.
[0360] As shown in FIG. 20, the relative tensile strength of foams made from PET9PEF1-EX16B copolymers, which contained a relatively low percentage of PEF moieties (about 10 mol%) and used 1234ze(E) as a blowing agent, resulted in superior relative tensile strength compared to foams made from PET1A and PET1B homopolymers and 1234ze(E) blowing agent.
[0361] One aspect of this unexpected result can be shown, for example, by noting that the relative tensile strength of the two foams made with PET9PEF1-EX16B copolymer at an RFD of about 0.062 had an average relative tensile strength of 0.89. In contrast, at this same RFD of about 0.062, the PET homopolymer had a relative tensile strength of about 0.52 based on the trend line of the PET data, as shown by the dashed line in the graph above. This represents a relative tensile strength of about 1.7 times greater for Applicants' PET9PEF1 foam in this example compared to the foam made from PET homopolymer. Similarly, at an RFD of about 0.088, the PET9PEF1 foam had a relative tensile strength of 1.41. In contrast, at this same RFD of about 0.088, the PET homopolymer foam had a relative tensile strength of about 0.75 based on the PET trend line. This represents a relative tensile strength of about 1.9 times greater for Applicants' PET9PEF1 foam. These are important and unexpected results.
[0362] Comparative Example C5 - Preparation of PET homopolymer with molecular weight of about 38 kg / mol using PMDA and SSP PET homopolymer was prepared by adding approximately 93 grams (0.3659 moles) of bis(2-hydroxyethyl) terephthalate (BHET) to a 500 mL round bottom flask. After evacuating and backfilling with N2, the flask was lowered into a 180°C salt bath and overhead mixing was started at 100 rpm under N2 flow. 0.13 grams (0.00045 moles) of titanium isopropoxide catalyst was added to the flask. After 1 hour, the bath temperature was increased to 230°C. After 30 minutes at this temperature under N2, vacuum was started and continued for 1 hour, then the temperature was further increased to 285°C. After 2 hours at 285°C, pyromellitic dianhydride PMDA (0.49 g, 0.0022 moles) was added slowly over approximately 10 minutes. After mixing for an additional 30 minutes at this temperature, the reaction was stopped. An aliquot (30 g) of the above product was ground and then solid state polymerized by heating in a rotary evaporator under vacuum at 180° C. for 3 days. The PET homopolymer so produced was tested and found to have the characteristics reported in Table C5 below.
[0363] [Table 58]
[0364] The PET polymer so produced is referred to in these examples as PETC3.
[0365] Comparative Example 6 - Preparation of PEF Foam Using PETC3 with 1234ze(E) Blowing Agent One gram of polymer (shown in Table C6 below) in a glass container was placed in an autoclave and then dried at 130°C under vacuum for 6 hours. The dried polymer was then cooled to room temperature and placed in a glass container in the autoclave. For each polymer, the blowing agent (shown in Table C6 below) was then pumped into the autoclave containing the dried polymer, followed by heating the autoclave to bring the polymer to the molten state and pressure shown in Table C6. The PET / blowing agent mixture was maintained in the molten state for about 1 hour, and then the melt / blowing agent temperature and pressure were reduced to the pre-expansion temperature and pre-expansion pressure shown in Table C6 over a period of about 5-15 minutes. The autoclave was then maintained at about this temperature and pressure for about 30 minutes to allow the amount of blowing agent incorporated in the melt under such conditions to reach equilibrium. The conditions used, such as the amount of blowing agent and the melt temperature and pressure, were determined after several trials based on the ability to form acceptable foams having RFD values of about 0.2 or less. The temperature and pressure inside the autoclave were then rapidly reduced (approximately 10 seconds for pressure reduction and approximately 1-10 minutes for temperature reduction using cold water) to ambient conditions (approximately 22° C. and 1 atm) to induce foaming.
[0366] The foam produced in this Comparative Example 6 was tested and found to have the properties as reported in Table C6 below.
[0367] [Table 59]
[0368] Example 17A - Preparation of PEF homopolymer with MW of 33 kg / mol using PMDA and SSP The PEF homopolymer was made using the same additives and basic polymer formation procedure used to form the PEF homopolymer of Comparative Example 3, achieving a polymer molecular weight of about 30,000 kg / mol. Specifically, the PEF homopolymer was formed by esterifying and polycondensing 2,5-furandicarboxylic acid with monoethylene glycol to form a PEF homopolymer according to methods consistent with those described herein, and then treated with 0.7 wt.% PMDA according to known techniques. The polymer then underwent solid-state polymerization consistent with the previous examples to form a PEF homopolymer. The PEF polymer was tested using the same measurement techniques described in Comparative Example 1 and found to have the properties reported in Table E17A below.
[0369] [Table 60]
[0370] The PEF polymer produced in this example is referred to above and hereafter as PEF-Ex17A.
[0371] Examples 17B-1 and 17B: Preparation of PEF foam using PEF-Ex17A and trans 1234ze as blowing agent Two foams were made from PEF-EX17A using a foaming process designed using the same criteria as described in these examples. The foams so produced were tested and found to have the properties reported in Table E17A below.
[0372] [Table 61]
[0373] Surprisingly, the tensile strength of the foam made from PEF homopolymer and 1234ze(E) blowing agent was dramatically better than that of the foam made from PET homopolymer and 1234ze(E) blowing agent. In this regard, it is important to note that the molecular weight of the PET used to make the PET foam (37.6K) is reasonably close to the molecular weight of the PEF foam (33K), thus making the data comparable in terms of molecular weight. This unexpected result can be illustrated, for example, by first taking the average of two PEF data points according to the present invention having an RFD of less than 0.1, and then noting that the average density of these two points is 0.0805 and the average relative tensile strength is 1.34. Nevertheless, compared to a PET foam having a density more than 2.4 times that of the foam made from the PEF of the present invention, the PEF foam of the present invention produces an average tensile strength equal to that of the PET foam. This is a very important and unexpected result.
[0374] Surprisingly, the compressive strength of the foam made from PEF homopolymer and 1234ze(E) blowing agent was dramatically better than that of the foam made from PET homopolymer and 1234ze(E) blowing agent. This unexpected result can be shown, for example, by first taking the average of two PEF data points according to the present invention having an RFD of less than 0.1 and noting that the average density of these two points is 0.0805 and the average relative compressive strength is 0.84. Nevertheless, compared to a PET foam having a density more than twice the average PEF foam density, the PEF foam of the present invention produces an average tensile strength equal to that of the PET foam. This is a very important and unexpected advantage of PEF foam compared to PET foam.
[0375] Example 18A - Preparation of PET9:PEF1 Copolymer with PET MW of about 133.8 kg / mole using PMDA and SSP A random copolymer of PET9:PEF1 (9:1 molar ratio) was prepared by adding 8.7 grams (0.0472 moles) of furandicarboxylic acid methyl ester (FDME), 106.8 grams (0.42 moles) of bis(2-hydroxyethyl) terephthalate (BHET), and 6.2 grams (0.1 moles) of EG to a 500 mL cylindrical steel reactor equipped with an overhead stirrer and distillation / condensation apparatus. After evacuating and backfilling with N2, 0.046 grams of Ti(IV) isopropoxide catalyst was added. The reactor was then placed in a salt bath at 180°C and overhead mixing was started at 200 rpm under N2 atmosphere. After 2.5 hours, the bath temperature was increased to 220°C. After 30 minutes under N2, vacuum was started. After 40 minutes under vacuum, the temperature was increased to 250°C and continued for 40 minutes. Under N2 atmosphere, 0.59 grams of PMDA (0.0.0027 moles) was slowly added. After mixing for an additional 30 minutes at temperature, the reaction was stopped. An aliquot (30 g) of the above product was ground and then subjected to solid state polymerization by heating in a rotary evaporator at 180° C. under vacuum for 3 days. The PEF polymer was tested and found to have the characteristics of Table E18A.
[0376] [Table 62]
[0377] The PET9:PEF1 random copolymer so produced is referred to in these examples as PET9PEF1-EX18A.
[0378] Examples 18B1, 18B2, and 18C3: Preparation of PETPEF copolymer foams using PET9PEF1-EX18A and Trans1234ze as the blowing agent Three types of foams were made from PET9PEF1-EX18A using a foaming process designed using the same criteria as described in Comparative Example 1. The foams so produced were tested and found to have the properties as reported in Table E18B below.
[0379] [Table 63]
[0380] As evidenced by the data in Table E18B above, Applicants have surprisingly found that foams made from PEF9:PET1-EX18A in accordance with the present invention have unexpectedly superior tensile strength than foams formed from PET homopolymer, as shown in FIG. 21, which includes PET tensile strength data from comparative examples for comparison purposes.
[0381] As shown in FIG. 21, the relative tensile strength of foams made from PET9PEF1-EX18A copolymers containing a relatively low percentage of PEF moieties (about 10 mol %) and using 1234ze(E) as the blowing agent resulted in superior relative tensile strength compared to foams made from comparative PET homopolymer foams, despite being formed from the preferred 1234ze(E) blowing agent of the present invention.
[0382] One aspect of this unexpected result can be shown, for example, by noting that the relative tensile strength of the two foams made with PET9PEF1-EX7 copolymer at an RFD of about 0.062 had an average relative tensile strength of 0.89. In contrast, at this same RFD of about 0.062, the PET homopolymer had a relative tensile strength of about 0.52 based on the trend line of the PET data, as shown by the dashed line in the graph above. This represents a relative tensile strength of about 1.7 times greater for Applicants' PET9PEF1 foam in this example compared to the foam made from PET homopolymer. Similarly, at an RFD of about 0.088, the PET9PEF1 foam had a relative tensile strength of 1.41. In contrast, at this same RFD of about 0.088, the PET homopolymer foam had a relative tensile strength of about 0.75 based on the PET trend line. This represents a relative tensile strength of about 1.9 times greater for Applicants' PET9PEF1 foam. These are important and unexpected results.
[0383] Example 19A - Preparation of PET1:PEF9 Copolymer with MW of approximately 85 kg / mol using PMDA and SSP A random copolymer of PET1:PEF9 (1:9 molar ratio) was prepared with a target molecular weight of approximately 85,000 g / mol. Specifically, 90.7 grams of FDME (0.49 moles), 13.9 grams of BHET (0.055 moles), and 64.1 grams of EG (1.03 moles) were added to a 500 mL round steel reactor equipped with an overhead stirrer and a distillation / condensation apparatus. After evacuating and backfilling with N2, 0.074 grams of Ti(IV) isopropoxide catalyst was added. The flask was then lowered into a salt bath at 180° C. and overhead mixing was started at 200 rpm under N2 atmosphere. After 2.5 hours, the bath temperature was increased to 220° C. After 30 minutes at this temperature under N2, a vacuum was started. After 40 minutes under vacuum, the temperature was increased to 250° C. and continued for 2 hours. Under N2 atmosphere, 0.68 grams of PMDA was slowly added. After mixing at temperature for an additional 30 minutes, the reaction was stopped. An aliquot (30 g) of the above product was ground and then solid-state polymerized by heating in a rotary evaporator at 180°C under vacuum for 3 days. The copolymer thus produced was a random copolymer with an overall molar ratio of PET:PEF of 1:9, and PET to PEF of 1:1. The PEF polymer was tested and found to have a molecular weight of about 85,100.
[0384] The PET1:PEF9 copolymer so produced is referred to in these examples as PET1PEF9-EX19A.
[0385] Example 19B - Preparation of PET1PEF9 Copolymer Foam Using PET1PEF9EX11 and Trans 1234ze as Blowing Agent One type of foam was made from PET1PEF9-EX19A using a foaming process designed using the same criteria as described in the Comparative Example. The foam thus produced was tested and found to have the properties as reported in Table E19B below.
[0386] [Table 64]
[0387] As evidenced by the data in Table E19B above, applicants have surprisingly found that foams made with PET1:PEF9-EX19A copolymers according to the present invention have unexpectedly superior tensile strengths than those of foams made from PET homopolymers. The tensile strength of foams made from PET1PEF9-EX19A copolymers containing about 10% PET moiety and using 1234ze(E) as a blowing agent resulted in dramatically superior tensile strengths compared to comparative PET homopolymers made with 1234ze(E) blowing agent. In this regard, it is important to note that the molecular weights of the PET homopolymers used to make the PET foams (83.9 kg / mol and 105.3 kg / mol) were sufficiently close to the molecular weights of the foams made with PET1PEF9-EX19A copolymers (85.1K) to make the data in favor of PET homopolymers comparable from a molecular weight standpoint.
[0388] One aspect of this unexpected result can be shown, for example, by noting that at an RFD of about 0.063, the tensile strength of a foam made with PET1PEF9 copolymer resulted in a tensile strength of 1.2. In contrast, at this same RFD of about 0.063, the PET homopolymer had a tensile strength of about 0.6 based on the trend line. This represents about a two-fold greater tensile strength for Applicants' PET1PEF9 foam in this example compared to a foam made from PET homopolymer. This is an important and unexpected result.
[0389] Example 20 - Preparation of PET9:PEF1 Copolymer with MW of about 65.7 kg / mol using PMDA Chain Extender and SSP A block copolymer of PET9:PEF1 (9:1 molar ratio) was prepared with a target molecular weight of about 65,000 g / mol and PET to PEF blocks of 1-5, 1-3. Specifically, the PEF was prepared by first adding 498 grams of FDCA (2.7 moles) and 417 grams of EG (6.72 moles) to a 1000 mL cylindrical glass reactor equipped with an overhead stirrer and distillation / condensation apparatus, which was then immersed in a salt bath at 190°C. After purging with nitrogen, 0.414 grams of Ti(IV) isopropoxide catalyst was added to the flask and overhead mixing was started at 200 rpm under N2 atmosphere. After 2.5 hours, the bath temperature was increased to 220°C. After 30 minutes at this temperature under N2, vacuum was initiated. After 40 minutes under vacuum, the temperature was increased to 240°C and continued for 2 hours before the reaction was stopped to produce PEF.
[0390] PEF oligomers were prepared by adding 109 grams of EG and 0.45 grams of sodium carbonate to a 500 mL cylindrical reactor equipped with a reflux condenser and overhead stirrer. The mixture was heated to boiling (196° C.) and then an aliquot of PEF (160 grams) from the above step was added. The mixture was allowed to react under reflux for 2 hours until the reaction stopped. The resulting mixture is PEF oligomers.
[0391] PET oligomers were prepared by adding EG (28 grams) and sodium carbonate (0.46 g) to a 500 mL cylindrical reactor equipped with a condenser and overhead stirrer. The mixture was heated to boiling (196° C.). Then 170 grams of commercial PET was added. The mixture was allowed to react under reflux for 2 hours until the reaction stopped. The result was a PET oligomer mixture.
[0392] The copolymer was made by rapidly adding 7.14 grams of PEF oligomer and 67.9 grams of PET oligomer to a 500 mL cylindrical steel reactor equipped with an overhead stirrer and distillation / condensation apparatus immersed in a salt bath at 220° C., followed by the addition of 0.84 grams of Ti(IV) isopropoxide. Shortly thereafter (<2 min), vacuum was applied to remove the EG. After 40 min, the temperature was increased to 270° C. and the reactor contents were held under vacuum for 40 min. Under a N2 atmosphere, 0.46 grams of PMDA was added slowly over approximately 5 min. After mixing at this temperature for an additional 30 min, the reaction was stopped. An aliquot (30 g) of this product was then ground and subsequently subjected to solid state polymerization by heating in a rotary evaporator at 180° C. under vacuum for 3 days.
[0393] The PET9:PEF1 copolymer was tested and found to have the properties of Table E20A.
[0394] [Table 65]
[0395] The PET:PEF block copolymer so produced is referred to in these examples as PET9PEF1-EX20A.
[0396] Examples 20B1, 20B2, and 20B3: Preparation of PETPEF copolymer foams using PET9PEF1-EX20A and Trans1234ze as the blowing agent Three types of foams were made from PET9PEF1-EX20A using a foaming process designed using the same criteria as described in the above examples. The foams so produced were tested and found to have the properties as reported in Table E20B below.
[0397] [Table 66]
[0398] As evidenced by the data in Table E20B above, applicants have surprisingly found that PET9:PEF1-EX20B copolymer foams according to the present invention have unexpectedly better tensile strength than foams made from comparative PET homopolymers, as shown in FIG. 20, which includes PET tensile strength data from comparative examples for comparison purposes. As shown, the compressive strength of foams made with the PET9PEF1 copolymer of the present invention and 1234ze(E) was as good as or, for foams having an RFD greater than 0.07, substantially and unexpectedly better than the compressive strength exhibited by foams made from PET homopolymers. Referring to the data above an RFD of 0.07, foams made from PET9PEF1 copolymer exhibited an average relative compressive strength of 1.065, while PET foams at this RFD had a compressive strength of about 0.7 based on the trend line. Thus, at densities above 0.07, foams made with PET9PEF1 copolymer and 1234ze(E) yielded 1.5 times higher compressive strength than foams made with PET homopolymer based on the PET data trend line, an important and unexpected result.
[0399] Example 21 - Preparation of PET1:PEF9 Copolymer with MW of about 25 kg / mole using PMDA and SSP A random copolymer of PET1:PEF9 (1:9 molar ratio) was prepared with a target molecular weight of approximately 25,000 g / mole and a PET to PEF block ratio of 1:1. Specifically, 40 grams of FDME (0.26 moles), 7.24 grams of BHET (0.0285 moles), and 31.8 grams of EG (0.5123 moles) were added to a 250 mL round bottom flask equipped with a stir bar. After evacuating and refilling with N2, the flask was lowered into a salt bath at 180° C. and overhead mixing was started at 100 rpm under N2 flow. 0.04 grams of Ti(IV) isopropoxide catalyst was then added. After 2.5 hours, the bath temperature was increased to 230° C. After 30 minutes at this temperature under N2, vacuum was started and continued for 2 hours. Under N2 atmosphere, 0.313 grams of PMDA was slowly added over approximately 10 minutes. After mixing at this temperature for an additional 30 minutes, the reaction was stopped. An aliquot (20 g) of the above product was ground and then subjected to solid state polymerization by heating in a rotary evaporator at 180° C. under vacuum for 3 days. The PET1:PEF9 copolymer was tested and found to have the properties of Table E21A.
[0400] [Table 67]
[0401] The resulting PET1:PEF9 random copolymer is referred to in these examples as PET1PEF9-EX21A.
[0402] Examples 21B1 and 21B2: Preparation of PETPEF copolymer foams using PET1PEF9-EX21A and Trans1234ze as the blowing agent Foams were made from PET1PEF9-EX21A using a foaming process designed using the same criteria as described in the above examples. The foams so produced were tested and found to have the properties as reported in Table E21B below.
[0403] [Table 68]
[0404] As evidenced by the data in Table E21B above, Applicants have surprisingly found that PEF foams from the PET1PEF9-EX21B copolymer of the present invention have unexpectedly superior tensile strength than foams formed from PET, as shown in FIG. 26, which includes PET tensile strength data from a comparative example for comparison purposes.
[0405] Synthesis Example Synthesis Example 1A1 41.2 kg / mole of PEF homopolymer was formed by esterification and polycondensation of 75 grams of 2,5-furandicarboxylic acid (FDCA) with 55 grams of monoethylene glycol (EG). The reactants were added to a 500 mL cylindrical steel reactor equipped with an overhead stirrer and a distillation / condensation apparatus. After pulling a vacuum and backfilling with nitrogen, 0.228 grams of titanium (IV) isopropoxide catalyst was added to the flask. The flask was then lowered into a salt bath at 180° C. and overhead mixing was started at 200 rpm under nitrogen. After 2.5 hours, the bath temperature was increased to 220° C. After 30 minutes at this temperature under nitrogen, vacuum was started. After 40 minutes under vacuum, the temperature was increased to 250° C. and continued for 1 hour. PMDA (0.5732 g) was added slowly over about 5 minutes under nitrogen flow. After mixing for an additional 30 minutes at this temperature, the reaction was stopped. To carry out the SSP, an aliquot of the product was ground and heated in a rotary evaporator under vacuum at 180° C. for 3 days to produce a PEF homopolymer with a molecular weight of 41 kg / mol as reported in Example 1A.
[0406] Synthesis example 1A2-75000 Specifically, 75 kg / mol PEF homopolymer was formed by esterification and polycondensation of 350 grams of 2,5-furandicarboxylic acid (FDCA) with 279 grams of monoethylene glycol (EG). The reactants were added to a 1 liter cylindrical steel reactor equipped with an overhead stirrer and a distillation / condensation apparatus. After pulling a vacuum and backfilling with nitrogen, 0.228 grams of titanium (IV) isopropoxide catalyst was added to the flask. The flask was then lowered into a salt bath at 180°C and overhead mixing was started at 200 rpm under nitrogen atmosphere. After 2.5 hours, the bath temperature was increased to 220°C. After 30 minutes at this temperature under nitrogen, vacuum was started. After 40 minutes under vacuum, the temperature was increased to 230°C and continued for 1 hour. PMDA (2.73 g-0.7 wt%) was added slowly over about 5 minutes under nitrogen flow. After mixing for an additional 30 minutes at this temperature, the reaction was stopped. To carry out the SSP, an aliquot of the product (30 g) was ground and heated in a rotary evaporator under vacuum at 180° C. for 3 days to produce a PEF homopolymer with a molecular weight of 75 kg / mol as reported in Example 1A.
[0407] Synthesis Example 2A1 - Preparation of PEF homopolymers with MW range of about 90 kg / mol using PMDA and SSP For the 90.8 kg / mol MW polymer, FDCA (75 g) and EG (54.6 g) were added to a 500 mL cylindrical steel reactor equipped with an overhead stirrer and a distillation / condensation apparatus. After pulling a vacuum and backfilling with nitrogen, 0.100 grams of titanium (IV) isopropoxide catalyst was added to the flask. The flask was then lowered into a 180° C. salt bath and overhead mixing was started at 200 rpm under nitrogen. After 2.5 hours, the bath temperature was increased to 220° C. After 30 minutes at this temperature under nitrogen, a vacuum was started. After 40 minutes under vacuum, the temperature was increased to 250° C. and continued for 2 hours. Under nitrogen flow, PMDA (0.587 g) was added slowly over approximately 5 minutes. After mixing for an additional 30 minutes at this temperature, the reaction was stopped. The product was removed from the vessel. γ-valerolactone was added to dissolve any remaining polymer in the reactor and on the impeller. The mixture was stirred at 190° C. for several hours. γ-Valerolactone was distilled from the polymer under vacuum to give a solid. To carry out SSP, an aliquot of the product (30 g) was ground and heated in a rotary evaporator at 180° C. under vacuum for 3 days to produce a PEF homopolymer with a molecular weight of 90.8 kg / mol as reported in Example 2A.
[0408] Synthesis Example 2A2 - Preparation of PEF homopolymer with MW range of about 96 kg / mol using PMDA and SSP For the 96,078 g / mol MW polymer, 75 grams of 2,5-furandicarboxylic acid (FDCA) and 55 grams of monoethylene glycol (EG). The reactants were added to a 500 mL cylindrical steel reactor equipped with an overhead stirrer and a distillation / condensation apparatus. After pulling a vacuum and backfilling with nitrogen, 0.228 grams of titanium (IV) isopropoxide catalyst was added to the flask. The flask was then lowered into a 180° C. salt bath and overhead mixing was started at 200 rpm under nitrogen. After 2.5 hours, the bath temperature was increased to 220° C. After 30 minutes at this temperature under nitrogen, vacuum was started. After 40 minutes under vacuum, the temperature was increased to 250° C. and continued for 1 hour. PMDA (0.5732 g) was added slowly over approximately 5 minutes under nitrogen flow. After mixing for an additional 30 minutes at this temperature, the reaction was stopped. To perform the SSP, an aliquot of the product was ground and heated in a rotary evaporator under vacuum at 180° C. for 3 days to produce a PEF homopolymer as reported below. The product was removed from the vessel. γ-valerolactone was added to dissolve the polymer remaining in the reactor and on the impeller. The mixture was stirred at 190° C. for several hours. γ-valerolactone was distilled from the polymer under vacuum to obtain a solid. To perform the SSP, an aliquot of the product was ground and heated in a rotary evaporator under vacuum at 180° C. for 3 days to produce a PEF homopolymer with a molecular weight of 96,078 as reported in Example 2A.
[0409] Synthesis Example 3A - Preparation of PET9:PEF1 Copolymer with MW of approximately 117.9:90.4 kg / mol using PMDA and SSP A block copolymer of PET9:PEF1 (9:1 molar ratio) was prepared with a target molecular weight of about 117,900 g / mol, with PET and PEF blocks being 4:4, respectively. Specifically, the PEF was prepared by first adding 498 grams of FDCA (2.7 moles) and 417 grams of EG (6.72 moles) to a 1000 mL cylindrical glass reactor equipped with an overhead stirrer and distillation / condensation apparatus, which was then immersed in a salt bath at 190°C. After purging with nitrogen, 0.414 grams of Ti(IV) isopropoxide catalyst was added to the flask and overhead mixing was started at 200 rpm under N2 atmosphere. After 2.5 hours, the bath temperature was increased to 220°C. After 30 minutes at this temperature under N2, vacuum was initiated. After 40 minutes under vacuum, the temperature was increased to 240°C and continued for 2 hours before the reaction was stopped to produce PEF.
[0410] PEF oligomers were prepared by adding 109 grams of EG and 0.45 grams of sodium carbonate to a 500 mL cylindrical reactor equipped with a reflux condenser and overhead stirrer. The mixture was heated to boiling in a salt bath at 230° C. An aliquot (160 grams) of PEF from the above step was added. The mixture was allowed to react under reflux for 2 hours until the reaction stopped. The resulting mixture is PEF oligomers.
[0411] PET oligomers were prepared by adding 103 grams of EG and 0.45 grams of sodium carbonate to a 500 mL cylindrical reactor equipped with a condenser and overhead stirrer. The mixture was heated in a salt bath at 230° C. Then, 160 grams of commercially available recycled PET flakes were added. The mixture was allowed to react under reflux for 2 hours until the reaction stopped. The result was a PET oligomer mixture.
[0412] The copolymer was made by rapidly adding 12.0 grams of PEF oligomer and 111.7 grams of PET oligomer to a 500 mL cylindrical steel reactor equipped with an overhead stirrer and distillation / condensation apparatus immersed in a salt bath at 220° C., followed by the addition of 0.9083 grams of Ti(IV) isopropoxide. Shortly thereafter (<2 min), vacuum was applied to remove the EG. After 40 min, the temperature was increased to 270° C. and the reactor contents were kept under vacuum for 40 min. Under a N2 atmosphere, 0.483 grams of PMDA was slowly added. After mixing at this temperature for an additional 30 min, the reaction was stopped. An aliquot (30 g) of the above product was ground and then solid-state polymerized by heating in a rotary evaporator at 180° C. under vacuum for 3 days to produce a PET9:PEF1 copolymer with a PET molecular weight of 117.9 kg / mol as reported in Example 3A.
[0413] Synthesis Example 5A - Preparation of PET9:PEF1 block copolymer with MW of about 44.9 kg / mol using PMDA and SSP A block copolymer of PET9:PEF1 (9:1 molar ratio) was prepared with a target molecular size of approximately 44,900 g / mol and 6 and 7 PET and PEF blocks, respectively.
[0414] PEF oligomers were prepared by adding 40.5 grams of EG and 0.174 grams of sodium carbonate to a 500 mL cylindrical reactor equipped with a reflux condenser and overhead stirrer. The mixture was heated to 230° C. until the catalyst was completely dissolved. Commercially available PEF (59.5 grams) was added and the mixture was refluxed under N2 for 2 hours. The resulting mixture is PEF oligomers.
[0415] PET oligomers were prepared by adding 235 grams of EG and 1.0 grams of sodium carbonate to a 1000 mL cylindrical reactor equipped with a condenser and overhead stirrer. The mixture was heated to 230° C. until the catalyst was completely dissolved. Commercially available PET (364 g) was added and the mixture was refluxed under N2 for 2 hours. The result was a PET oligomer mixture.
[0416] The copolymer was made by rapidly adding 12 grams of PEF oligomer and 111.7 grams of PET oligomer (both soluble at 160°C) to a 500 mL cylindrical steel reactor equipped with an overhead stirrer and distillation / condensation apparatus immersed in a salt bath at 220°C, followed by the addition of 0.8847 grams of Ti(IV) isopropoxide. Shortly thereafter (<2 minutes), vacuum was slowly applied to remove the EG. After 40 minutes, the temperature was increased to 270°C and the reactor contents were maintained under vacuum for 40 minutes. Under a N2 atmosphere, 0.483 grams of PMDA was slowly added. After mixing at this temperature for an additional 30 minutes, the reaction was stopped to give a polymer with a molecular weight of ~34,900 g / mol. An aliquot of this sample was sized to 60M and crystallized at 165°C under N2 for 4 hours. The above crystallized product was then subjected to solid-state polymerization by heating at 180° C. under vacuum in a rotary evaporator for 1 day to produce a PET9:PEF1 copolymer with a PET molecular weight of 117.9 kg / mol, as reported in Example 5A.
[0417] Synthesis Example 6A1 - Preparation of PET99:PEF1 random copolymer with MW of about 97.2 kg / mol using PMDA and SSP A random copolymer of PET99:PEF1 (99:1 molar ratio) was prepared by adding 0.68 grams (0.0037 moles) of furandicarboxylic acid methyl ester (FDME), 93.0 grams (0.366 moles) of bis(2-hydroxyethyl) terephthalate (BHET), and 0.46 grams (0.0074 moles) of EG to a 500 mL round bottom flask equipped with an overhead stirrer and a distillation / condensation apparatus. After evacuating and backfilling with N2, 0.138 grams of Ti(IV) isopropoxide catalyst was added. The reactor was then placed in a salt bath at 180° C. and overhead mixing was started at 100 rpm under N2 atmosphere. After 1 hour, the bath temperature was increased to 230° C. After 30 minutes, the temperature was increased to 270° C. After 2.5 hours at this temperature under N2, vacuum was started and continued for 3 hours. Under N2 atmosphere, 0.50 grams of PMDA (0.0.0023 moles) was slowly added. After mixing for an additional 25 minutes at temperature, the mixer was stopped, yielding a polymer with a molecular weight of ∼58,000 g / mol. An aliquot of the above product was ground and then solid-state polymerized by heating in a rotary evaporator at 180°C under vacuum for 1 day to produce a PET99:PEF1 copolymer with a PET molecular weight of 97,190 g / mol as reported in Example 6A.
[0418] A variation of this procedure was used to prepare a PET99:PEF1 copolymer with a PET molecular weight of 92,190 g / mol, as reported in Example 6A.
[0419] Synthesis Examples 8A1 and 8A2 - Preparation of PET19:PEF1 random copolymers with MW of approximately 72 and 79 kg / mol using PMDA and SSP A random copolymer of PET95:PEF5 (95:5 molar ratio) was prepared by adding 3.54 grams (0.0192 moles) of furandicarboxylic acid methyl ester (FDME), 93.0 grams (0.366 moles) of bis(2-hydroxyethyl) terephthalate (BHET), and 2.39 grams (0.0385 moles) of EG to a 500 mL round bottom flask equipped with an overhead stirrer and a distillation / condensation apparatus. After evacuating and backfilling with N2, 0.144 grams of Ti(IV) isopropoxide catalyst was added. The reactor was then placed in a salt bath at 180° C. and overhead mixing was started at 100 rpm under N2 atmosphere. After 1 hour, the bath temperature was increased to 230° C. After 30 minutes, the temperature was increased to 270° C. After 1 hour at this temperature under N2, vacuum was started and continued for 2 hours. Under N2 atmosphere, 0.515 grams of PMDA (0.0.0024 moles) was slowly added. Mixing at temperature for another 30 minutes gave a polymer with a molecular weight of ~40,000 g / mole. An aliquot of the above product was ground and then solid-state polymerization was carried out by heating in a rotary evaporator at 180°C under vacuum for 1 day to produce a PET19:PEF1 copolymer with a PET molecular weight of 72.6 kg / mole as reported in Example 7A1.
[0420] A variation of this procedure was used to produce a PET19:PEF1 copolymer with a PET molecular weight of 79 kg / mol, as reported in Example 7A2. Specifically, a random copolymer of PET95:PEF5 (95:5 molar ratio) was prepared by adding 3.54 grams (0.0192 moles) of furandicarboxylic acid methyl ester (FDME), 93.0 grams (0.366 moles) of bis(2-hydroxyethyl) terephthalate (BHET), and 2.39 grams (0.0385 moles) of EG to a 500 mL round bottom flask equipped with an overhead stirrer and a distillation / condensation apparatus. After evacuating and backfilling with N2, 0.144 grams of Ti(IV) isopropoxide catalyst was added. The reactor was then placed in a salt bath at 180°C and overhead mixing was started at 100 rpm under a N2 atmosphere. After 1 hour, the bath temperature was increased to 230°C. After 30 minutes, the temperature was increased to 270°C. After 1 hour at this temperature under N2, vacuum was started and continued for 2 hours. Under N2 atmosphere, 0.515 grams of PMDA (0.0.0024 moles) was slowly added. Mixing at temperature for another 30 minutes gave a polymer with a molecular weight of -40,000 g / mole. An aliquot of the above product was ground and then solid state polymerization was carried out by heating in a rotary evaporator at 180°C under vacuum for 1 day to produce a PET19:PEF1 copolymer with a PET molecular weight of 79 kg / mole as reported in Example 7A2.
[0421] Synthesis Example 11A - Preparation of PET95:PEF5 block copolymer with MW of about 83 kg / mol using PMDA A block copolymer of PET95:PEF5 (95:5 molar ratio) was prepared with a target molecular size of about 83,000 g / mol, and PET and PEF blocks of 7:7, respectively. The PEF oligomer was prepared by adding 40.5 grams of EG and 0.174 grams of sodium carbonate to a 500 mL cylindrical reactor equipped with a reflux condenser and an overhead stirrer. The mixture was heated to 230° C. until the catalyst was completely dissolved. Commercially available PEF (59.5 grams) was added and the mixture was refluxed under N2 for 2 hours. The resulting mixture is the PEF oligomer.
[0422] PET oligomers were prepared by adding 235 grams of EG and 1.0 grams of sodium carbonate to a 1000 mL cylindrical reactor equipped with a condenser and overhead stirrer. The mixture was heated to 220° C. until the catalyst was completely dissolved. Commercially available PET (364 g) was added and the mixture was refluxed under N2 for 2 hours. The result was a PET oligomer mixture.
[0423] The copolymer was made by rapidly adding 6 grams of PEF oligomer and 117.9 grams of PET oligomer (both soluble at 160° C.) to a 500 mL cylindrical steel reactor equipped with an overhead stirrer and distillation / condensation apparatus immersed in a salt bath at 220° C., followed by the addition of 0.892 grams of Ti(IV) isopropoxide. Shortly thereafter (<2 minutes), vacuum was slowly applied to remove the EG. After 40 minutes, the temperature was increased to 270° C. and the reactor contents were maintained under vacuum for 40 minutes. Under a N2 atmosphere, 0.483 grams of PMDA was slowly added. After mixing at this temperature for an additional 30 minutes, the reaction was stopped to produce a PET19:PEF1 copolymer with a PET molecular weight of 83.033 g / mol, as reported in Example 11A.
[0424] Synthesis Example 12 Preparation of PET9:PEF1 copolymer with MW of about 56 kg / mol using A1-ADR A random copolymer of PET9:PEF1 (9:1 molar ratio) was prepared by adding 8.7 grams (0.0472 moles) of furandicarboxylic acid methyl ester (FDME), 107.6 grams (0.42 moles) of bis(2-hydroxyethyl) terephthalate (BHET), and 6.22 grams (0.1 moles) of EG to a 500 mL cylindrical steel reactor equipped with an overhead stirrer and distillation / condensation apparatus. After evacuating and backfilling with N2, 0.0503 grams of Ti(IV) isopropoxide catalyst was added. The reactor was then placed in a salt bath at 180° C. and overhead mixing was started at 200 rpm under N2 atmosphere. After 2.5 hours, the bath temperature was increased to 220° C. After 30 minutes under N2, vacuum was started. After 40 minutes under vacuum, the temperature was increased to 250° C. and continued for 2 hours. Under N2 atmosphere, 1.1507 grams of ADR-4468 was slowly added. After mixing for an additional 30 minutes at temperature, the reaction was stopped. An aliquot (30 g) of the above product was ground and then solid-state polymerized by heating in a rotary evaporator at 180°C under vacuum for 3 days to produce a PET9:PEF1 copolymer with a PET molecular weight of 56,794 g / mol as reported in Example 12A1.
[0425] Synthesis Example 12A2 - Preparation of PEF homopolymer with MW of about 70 kg / mol using PMDA + talc and SSP A block copolymer of PET9:PEF1 (9:1 molar ratio) was prepared with a target molecular weight of about 117,900 g / mol, with 5 and 4 PET and PEF blocks, respectively. Specifically, the PEF was prepared by first adding 498 grams of FDCA (2.7 moles) and 417 grams of EG (6.72 moles) to a 1000 mL cylindrical glass reactor equipped with an overhead stirrer and distillation / condensation apparatus, which was then immersed in a salt bath at 190°C. After purging with nitrogen, 0.414 grams of Ti(IV) isopropoxide catalyst was added to the flask and overhead mixing was started at 200 rpm under N2 atmosphere. After 2.5 hours, the bath temperature was increased to 220°C. After 30 minutes at this temperature under N2, vacuum was initiated. After 40 minutes under vacuum, the temperature was increased to 240°C and continued for 2 hours before the reaction was stopped to produce PEF.
[0426] PEF oligomers were prepared by adding 109 grams of EG and 0.45 grams of sodium carbonate to a 500 mL cylindrical reactor equipped with a reflux condenser and overhead stirrer. The mixture was heated to boiling in a salt bath at 230° C. An aliquot (160 grams) of PEF from the above step was added. The mixture was allowed to react under reflux for 2 hours until the reaction stopped. The resulting mixture is PEF oligomers.
[0427] PET oligomers were prepared by adding 136 grams of EG and 0.68 grams of sodium carbonate to a 500 mL cylindrical reactor equipped with a condenser and overhead stirrer. The mixture was heated in a salt bath at 230° C. Then, 210 grams of commercially available recycled PET flakes were added. The mixture was allowed to react under reflux for 2 hours until the reaction stopped. The result was a PET oligomer mixture.
[0428] The copolymer was made by rapidly adding 10.15 grams of PEF oligomer and 97.64 grams of PET oligomer to a 500 mL cylindrical steel reactor equipped with an overhead stirrer and distillation / condensation apparatus immersed in a salt bath at 220° C., followed by the addition of 0.957 grams of Ti(IV) isopropoxide. Shortly thereafter (<2 minutes), vacuum was applied to remove the EG. After 40 minutes, the temperature was increased to 270° C. and the reactor contents were maintained under vacuum for 40 minutes. Under a N2 atmosphere, a mixture of 0.4615 grams of PMDA and 0.3317 grams of talc was slowly added. After mixing for an additional 30 minutes at this temperature, the reaction was stopped. An aliquot of the above product was ground and then subjected to solid state polymerization by heating in a rotary evaporator at 180° C. under vacuum for 3 days to produce a PET9:PEF1 copolymer with a PET molecular weight of 69,900 g / mol as reported in Example 12A2.
[0429] Synthesis Example 13A - Preparation of PET9:PEF1 block copolymer with MW of about 47 kg / mol using pentaerythritol A block copolymer of PET9:PEF1 (9:1 molar ratio) was prepared with a target molecular size of approximately 47,000 g / mol and 6 and 7 PET and PEF blocks, respectively.
[0430] PEF oligomers were prepared by adding 40.5 grams of EG and 0.174 grams of sodium carbonate to a 500 mL cylindrical reactor equipped with a reflux condenser and overhead stirrer. The mixture was heated to 230° C. until the catalyst was completely dissolved. Commercially available PEF (59.5 grams) was added and the mixture was refluxed under N2 for 2 hours. The resulting mixture is PEF oligomers.
[0431] PET oligomers were prepared by adding 235 grams of EG and 1.0 grams of sodium carbonate to a 1000 mL cylindrical reactor equipped with a condenser and overhead stirrer. The mixture was heated to 230° C. until the catalyst was completely dissolved. Commercially available PET (364 g) was added and the mixture was refluxed under N2 for 2 hours. The result was a PET oligomer mixture.
[0432] The copolymer was made by rapidly adding 12 grams of PEF oligomer and 111.7 grams of PET oligomer (both soluble at 160° C.) to a 500 mL cylindrical steel reactor equipped with an overhead stirrer and distillation / condensation apparatus immersed in a salt bath at 220° C., followed by the addition of 0.332 grams of pentaerythritol and 0.9 grams of Ti(IV) isopropoxide. Shortly thereafter (<2 min), vacuum was slowly applied to remove the EG. After 40 min, the temperature was increased to 270° C. and the reactor contents were held under vacuum for 40 min.
[0433] Synthesis Example C1A - Preparation of PET homopolymer with MW of about 105 kg / mol using PMDA and SSP Approximately 163 grams of bis(2-hydroxyethyl) terephthalate (BHET) and 0.114 grams of titanium(IV) isopropoxide were added to a 500 mL cylindrical reactor. The reactor was then lowered into a salt bath at 180° C. and overhead mixing was started at 200 rpm under N2 atmosphere. After 1.5 hours, the bath temperature was increased to 250° C. After 30 minutes at this temperature under N2, vacuum was started. After 40 minutes under vacuum, the temperature was increased to 280° C. and continued for 1 hour. Under N2 atmosphere, 0.66 grams of PMDA was added slowly over about 5 minutes. After mixing at this temperature for an additional 30 minutes, the reaction was stopped. An aliquot (30 g) of the above product was ground and then subjected to solid state polymerization by heating in a rotary evaporator at 180° C. under vacuum for 3 days.
[0434] Synthesis Example C2A1 - Preparation of PET homopolymer with a molecular weight of 95.6 kg / mol using PMDA and SSP PET homopolymer was prepared by polycondensation to give a product with a molecular size of 48.3 kg / mole. Approximately 93 grams (0.366 moles) of bis(2-hydroxyethyl) terephthalate (BHET) was added to a 500 mL round bottom flask. After drawing a vacuum and backfilling with N2, the flask was lowered into a salt bath at 180° C. and overhead mixing was started at 100 rpm under N2 flow. 0.129 grams (0.0005 moles) of titanium isopropoxide catalyst was placed in the flask. After 50 minutes, the bath temperature was increased to 285° C. After 2 hours at this temperature under N2, vacuum was started and continued for 2 hours. Under N2 flow, pyromellitic dianhydride PMDA (0.49 g, 0.0022 moles) was added slowly over approximately 10 minutes. After mixing for an additional 30 minutes at this temperature, the reaction was stopped. An aliquot (30 g) of the above product was ground and then solid state polymerized by heating in a rotary evaporator at 180° C. under vacuum for 3 days to give a polymer with a molecular weight of 95.6 kg / mol.
[0435] Synthesis Example C2A2 - Preparation of PET homopolymer with molecular weight of 80.87 kg / mol using PMDA and SSP PET homopolymer was prepared by polycondensation to give a product with a molecular size of 80,871 g / mol. Approximately 93 grams (0.366 moles) of bis(2-hydroxyethyl) terephthalate (BHET) was added to a 500 mL round bottom flask. After drawing a vacuum and backfilling with N2, the flask was lowered into a salt bath at 180°C and overhead mixing was started at 100 rpm under N2 flow. 0.123 grams (0.0004 moles) of titanium isopropoxide catalyst was placed in the flask. After 3 hours, the bath temperature was increased to 285°C. After 1 hour at this temperature under N2, vacuum was started and continued for 1 hour. Under N2 flow, pyromellitic dianhydride PMDA (0.49 g, 0.0022 moles) was added slowly over approximately 10 minutes. After mixing for an additional 30 minutes at this temperature, the reaction was stopped. An aliquot of the above product was ground and then solid state polymerized by heating in a rotary evaporator under vacuum at 180° C. for 3 days to give a polymer with a molecular weight of 80.9 kg / mol.
[0436] Synthesis Example C2A3 - Preparation of PET homopolymer with molecular weight of 80.9 kg / mol using PMDA and SSP PET homopolymer was prepared by polycondensation to give a product with a molecular size of 61.1 kg / mole. Approximately 93 grams (0.366 moles) of bis(2-hydroxyethyl) terephthalate (BHET) was added to a 500 mL round bottom flask. After drawing a vacuum and backfilling with N2, the flask was lowered into a salt bath at 180° C. and overhead mixing was started at 100 rpm under N2 flow. After heating for 3 hours under N2, 0.123 grams (0.0004 moles) of titanium isopropoxide catalyst was placed in the flask. After 50 minutes, the bath temperature was increased to 285° C. After 1.5 hours at this temperature under N2, vacuum was started and continued for 2 hours. Under N2 flow, pyromellitic dianhydride PMDA (0.49 g, 0.0022 moles) was added slowly over approximately 10 minutes. After mixing for an additional 30 minutes at this temperature, the reaction was stopped. An aliquot (30 g) of the above product was ground and then solid state polymerized by heating in a rotary evaporator under vacuum at 180° C. for 3 days to give a polymer with a molecular weight of 81 kg / mol.
[0437] Usage example Comparative Example 7: Wind turbine generator made using PET foam A wind turbine generator having a configuration of the general type shown in Figures __-__ of this specification is constructed on land with a nacelle approximately 150 meters above ground (relative to the centerline of the nacelle). The blade span of each blade from the hub axis to the blade tip is approximately 100 meters and the rotor diameter is approximately 200 meters. The generator produces approximately 13 MW of power at peak design conditions. In the blade design where PET is the only core material used, each of the three blades has a rotor shell length of 26.4 m. 3 of surface-treated commercial PET foam, totaling 79.2 m for all three blades. 3 PET is about 100kg / m 3Since the foam has a density of 1.5 MPa, the total weight of the PET foam for the wind turbine is 7900 kg. The PET foam provides a foam core compressive strength of 1.5 MPa and a foam core tensile strength of 2.5 MPa based on technical data sheets provided by commercial PET foam suppliers, i.e., Gurit, AArmacel.
[0438] Example 22A: Wind Turbine Generator Made with PEF Homopolymer Foam of the Present Invention A wind turbine is constructed having the configuration described in Comparative Example 7, except that the foam core is either a foam of the present invention including each of Foams 1-4, or a foam made from a PEF polymer of the present invention including thermoplastic polymers TPP1A-TPP22E, or a foam described in Examples 1-22. The high relative tensile strength of the preferred PEF foam of the present invention relative to PET foam allows for a density of about 1.2 to about 1.4 times lower for the PEF foam of the present invention relative to commercially available PET foam, while being comparable to the tensile strength of high density PET foam. Taking these strength advantages into account, the PEF-based wind turbine blade of this example is 1.3 times lighter than the foam portion of the PET-based blade of Comparative Example 4, while achieving the same energy production. According to the 2011 Sandia Report SAND2011-3779 (https: / / energy.sandia.gov / wp-content / gallery / uploads / 113779.pdf), the blade of a 13 MW wind turbine (100 m blade) is 20% foam core by weight. A 1.3 times reduction in foam weight results in a 5% reduction in blade weight. To balance the torque, this weight reduction in the turbine blade results in a further reduction in the weight of the nacelle, the final value depending on the distance between the center of mass of the nacelle to the tower. This overall weight reduction for the wind turbine as a result of using any of the foams of the present invention, including each of Foams 1-4, or foams made from the PEF polymers of the present invention, including thermoplastic polymers TPP1A-TPP22E, or foams described in Examples 1-22, is a highly advantageous and unexpected result.
[0439] Example 15B: Wind Turbine Generator Made with the PET:PEF Copolymer Foam of the Present Invention in the Blade Shell A wind turbine generator is made having the configuration described in Comparative Example 4, except that the foam core is either a foam of the invention including each of Foams 1-4, or a foam made from a PEF polymer of the invention including thermoplastic polymers TPP1A-TPP22E, or a foam as described in Examples 1-22. The preferred copolymer foams exhibit approximately two times higher tensile and compressive strength at a density comparable to that of the PET foam of the comparative example. Based on publicly available information from a commercial PET foam supplier as a baseline for comparison, it is believed that the preferred PET-PEF copolymer foams of the invention have a shear strength advantage that is approximately the average of the tensile and compressive strength advantages, approximately two times higher than PET foam. This two-fold advantage in shear strength is an unexpected and highly advantageous result, at least in part because, as expected, the thickness of the core foam can be reduced by a factor of two while still providing acceptable bending stiffness of the foam core. This is illustrated by the following calculations, given in Chapter 3 of Introduction to Sandwich Structures, Student Edition, 1995, Dan Zenkert. τ c =T x / d During the ceremony, T x is the direct load in Newtons (per width of the beam, which in this case is 1 cm) that causes bending of the beam (in this case the blade). d is the thickness of the core foam plus skin, approximately equal to the thickness of the core foam in cm. τ c is the shear stress experienced by the core foam as a result of the direct load. Since the load here is in Newtons / cm, the stress has units of pressure, Newtons / cm 2 High shear strength is due to high shear stress (τ c ) allowing for a thinner core foam thickness while still handling the same direct load on the beam.
[0440] Based on published data from commercial PET foam suppliers, we set the density of PET foam at 80 kg / m 3 from 135kg / m 3 Increasing the spacing between the foam and the PET foam increases the compressive and tensile strengths by 2.5 and 1.5 times, respectively. In this interval, the shear strength increases by about 2 times, which is roughly the average of the tensile and compressive strength advantages. The advantages determined in this example are based on information and data contained in the following publicly available sources, each of which is incorporated herein by reference: https: / / www.gurit.com / - / media / Gurit / Datasheets / Kerdyn-Green.pdf;(https: / / local.armacell.com / fileadmin / cms / pet-foams / ArmaPET_website / Product_Flyer / ArmaPET_Struct_GR)
[0441] Example 23: Wind Turbine Generator Made Using the Present Invention's PET:PEF Copolymer Foam in the Blade Shell A wind turbine generator is made having the configuration described in Comparative Example 7, except that the foam core is either a foam of the invention including each of Foams 1-4, or a foam made from a PEF polymer of the invention including thermoplastic polymers TPP1A-TPP22E, or a foam as described in Examples 1-22. The copolymer foam of the invention has a relative tensile strength that is about 1.7 times higher than the relative tensile strength of the comparative PET foam at comparable density. The copolymer foam of the invention also has a relative compressive strength that is about 1.5 times higher than the relative compressive strength of the comparative PET foam at comparable density. These results indicate that the copolymer foam of the invention has a shear strength that is about 1.6 times higher than the comparable PET foam, making it possible, and expected to be so, to reduce the thickness of the foam core by as much as about 1.6 times, as long as the bending stiffness of the foam core is still adequate. Reducing the thickness of the foam core results in a significant reduction in weight, which is a very advantageous, but unexpected, result.
Claims
1. 1. A low density thermoplastic foam comprising: (a) thermoplastic polymer cells comprising cell walls forming closed cells, said thermoplastic polymer consisting essentially of ethylene furanoate moieties and optional ethylene terephthalate moieties, said polymer comprising from about 1 mol % to about 100 mol % ethylene furanoate moieties, and optionally at least about 1 mol % ethylene terephthalate moieties; (b) contained within said closed cells, one or more HFOs having 3 or 4 carbon atoms and / or one or more HFCOs having 3 or 4 carbon atoms.
2. 10. The low density thermoplastic foam of claim 1, wherein the thermoplastic polymer has a crystallinity of at least about 5%.
3. 10. The low density thermoplastic foam of claim 1, wherein the polymer consists essentially of from about 1 mol % to about 100 mol % ethylene furanoate moieties and at least about 1 mol % ethylene terephthalate moieties.
4. 2. The low density thermoplastic foam of claim 1, wherein the thermoplastic polymer has a molecular weight of at least about 10,000 kg / mol and a crystallinity of at least about 5%, and consists essentially of ethylene furanoate and ethylene terephthalate moieties, the polymer comprising from about 1 mol % to about 20 mol % ethylene furanoate moieties and at least about 80 mol % ethylene terephthalate moieties.
5. 2. The low density thermoplastic foam of claim 1, wherein the thermoplastic polymer has a molecular weight of at least about 10,000 kg / mol and a crystallinity of at least about 5%, and consists essentially of ethylene furanoate and ethylene terephthalate moieties, the polymer comprising from about 0.5 mol % to about 2 mol % ethylene furanoate moieties and from about 98 mol % to about 99.5 mol % ethylene terephthalate moieties.
6. 2. The low density thermoplastic foam of claim 1, wherein the one or more HFOs having 3 or 4 carbon atoms and / or the one or more HFCOs having 3 or 4 carbon atoms comprise one or more of 1234ze(E), 1336mzz, and 1233zd.
7. 2. The low density thermoplastic foam of claim 1, wherein the one or more HFOs having 3 or 4 carbon atoms and / or the one or more HFCOs having 3 or 4 carbon atoms consist essentially of one or more of 1234ze(E), 1336mzz(Z) and 1233zd(E).
8. 1. A method of forming a thermoplastic foam for use in a wind energy device, comprising: (a) a foamable composition, the foamable composition comprising: (c) a thermoplastic material consisting essentially of ethylene furanoate portions and optional ethylene terephthalate portions, said thermoplastic material comprising from about 1 mol % to about 100 mol % ethylene furanoate portions, and optionally at least about 1 mol % ethylene terephthalate portions; (d) providing a blowing agent comprising one or more HFOs having 3 or 4 carbon atoms and / or one or more HFCOs having 3 or 4 carbon atoms; (b) foaming the foamable composition.
10. 1. A method for forming a thermoplastic composition having improved crystallinity, comprising: (d) forming a thermoplastic material comprising polymer chains containing ethylene furanoate and / or ethylene terephthalate moieties; (e) dissolving at least a portion of said thermoplastic material in a solvent, said thermoplastic material comprising from about 1 mol % to about 100 mol % ethylene furanoate moieties, and optionally at least about 1 mol % ethylene terephthalate moieties; (f) distilling the solvent from the thermoplastic material.
Citation Information
Patent Citations
Composition containing fluorine substituted olefin
JP2010265471A
Polyphenylene sulfide-based resin composition and molding or the like comprising the resin composition as base material
JP2013155288A
Compositions containing fluorine substituted olefins
JP2013227580A
Foamable thermoplastic composition, thermoplastic foam and method for producing same
JP2024531277A
Expandable thermoplastic composition, thermoplastic foam and method for producing same
JP2024531287A